Metallic compound inclusion
The use of a metal compound-containing material forms metal-carbon composite films on carbon substrates, addressing the limitations of CVD devices by enabling film application on non-standard shapes and sizes while enhancing durability and efficiency.
Patent Information
- Application Number
- JP2024105584
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Existing methods for forming protective films on carbon substrates using CVD devices are limited by the size and shape of the base material and require significant time, making it difficult to apply films to non-standard shapes and sizes.
A metal compound-containing material, comprising Ti, Nb, Mo, Hf, Ta, W, Zr, and Si, is used to form a metal-carbon composite film on carbon substrates without a CVD device, allowing for the formation of protective films on various shapes and sizes by reacting with carbon to create metal carbides.
The solution enables the formation of protective films on carbon substrates of any size or shape, improving durability and reducing processing time compared to CVD methods.
Smart Images

Figure 2025010051000008 
Figure 2025010051000009 
Figure 2025010051000010
Abstract
Description
[Technical field]
[0001] The present invention relates to metal compound-containing materials. [Background technology]
[0002] For components that require heat resistance or reactivity resistance (for example, oxidation resistance or chemical resistance), the heat resistance or reactivity resistance can be improved and the life of the component can be extended by forming a protective film of a metal compound or the like on the surface of the base material.
[0003] For example, when forming a tantalum carbide layer as a protective film on the surface of a carbon substrate, as disclosed in Patent Document 1, a CVD apparatus is generally used. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2004 / 009515 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the size and shape of the substrate on which a protective film can be formed is predetermined for each CVD device, and depending on the size and shape of the substrate, it was not possible to form a protective film on the surface. Also, the process of forming a protective film on the surface of a substrate using a CVD device took a considerable amount of time.
[0006] In view of the above problems, the present invention provides a metal compound-containing material that can form a protective film on a carbon substrate without the need for a CVD apparatus. [Means for solving the problem]
[0007] The metal compound-containing material of the present invention, which has been made to solve the above-mentioned problems, is a metal compound-containing material for forming a metal-carbon composite coating on a carbon substrate, and is characterized in that the metal compound-containing material contains a compound of at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si. In the present specification, the term "metal-carbon composite coating" may refer to a coating in which a metal element and a carbon element are bonded together, such as a metal carbide alone or a carbon-containing material containing a metal carbide. The coating may also refer to a coating in which a metal compound other than the metal carbide is dispersed in the carbon-containing material, that is, the metal element and the carbon element are not bonded together but are mixed or dispersed together. Examples of the metal compound other than the metal carbide include metal oxides, metal nitrides, metal sulfides, and metal hydroxides.
[0008] The metal compound-containing material of the present invention includes at least one compound of a metal element selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si. Specifically, peroxo complex metal compounds (e.g., peroxohydroxy acid complex metal compounds, peroxocitrate complex metal compounds, and peroxoammonium complex metal compounds) containing at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si, metal hydroxides, hydroxy acid complex metal compounds (e.g., ammonium oxalate complex metal compounds), and polyacids are included, but are not limited to these compounds. In addition, the metal compound-containing material may contain a metal element, a semimetal element, or a nonmetal element other than at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si. For example, B, P, etc. may be included.
[0009] When the metal compound-containing material is a peroxo complex metal compound, even if the substrate does not contain carbon, the metal element contained in the peroxo complex metal compound reacts with carbon to form a metal carbide by heating the substrate coated with the peroxo complex metal compound. When the metal compound-containing material is a hydroxy acid complex metal compound, the metal element contained in the hydroxy acid complex metal compound reacts with carbon to form a metal carbide.
[0010] The content of the metal compound-containing material is preferably adjusted according to the type of metal element or carbon substrate, and is more preferably more than 0 mass% and not more than 40 mass%, further preferably 0.1 mass% to 30 mass%, particularly preferably 0.2 mass% to 30 mass%, and particularly preferably 0.3 mass% to 15 mass%. When the metal compound-containing material contains a plurality of metal elements selected from Ti, Nb, Mo, Hf, Ta, W, and Zr, the total value of each mass fraction is preferably within the above-mentioned numerical range.
[0011] Here, the mass fraction of the metal compound-containing material may be calculated by diluting the metal compound-containing material appropriately with dilute hydrochloric acid as necessary, and measuring the mass fraction in metal equivalent using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.
[0012] The metal compound-containing material of the present invention is also characterized in that the content of a compound of at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si is more than 0 mass% and not more than 35 mass%, calculated as the metal. The content of at least one metal element compound selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si in the metal compound-containing material is preferably adjusted according to the type of metal element and carbon-based substrate, and is more preferably more than 0 mass% and 35 mass% or less, more preferably 0.03 mass% or more and 25 mass% or less, particularly preferably 0.06 mass% or more and 25 mass% or less, and particularly preferably 0.1 mass% or more and 15 mass% or less, in terms of metal. In addition, when the metal compound-containing material contains multiple metal elements selected from Ti, Nb, Mo, Hf, Ta, W, and Zr, it is preferable that the total value of the mass fractions of each metal is within the above-mentioned numerical range. In this specification, metal conversion means Ti conversion, Nb conversion, Mo conversion, Hf conversion, Ta conversion, W conversion, Zr conversion, and Si conversion. The metal compound-containing material may contain metal elements, semimetal elements, and nonmetal elements other than at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si. For example, B, P, etc. may be included.
[0013] The metal compound-containing material of the present invention may also contain a Ta compound. The metal compound-containing material preferably contains a Ta compound, since it reacts with the carbon contained on the carbon substrate and facilitates the carbonization reaction.Specific examples of the Ta compound include a tantalum peroxocitrate compound, a tantalum hydroxide, and a polyoxotantalate.
[0014] When the metal compound-containing material is a tantalum peroxocitrate compound, even if the substrate does not contain carbon, by heating the substrate to which the tantalum peroxocitrate compound is applied, the tantalum contained in the tantalum peroxocitrate compound reacts with carbon to form tantalum carbide.
[0015] Furthermore, when the metal compound-containing material is a tantalic acid hydroxide, the tantalum concentration in the metal compound-containing material may typically be 5 mass% or more and 30 mass% or less, 5 mass% or more and 25 mass% or less, 5 mass% or more and 20 mass% or less, 5 mass% or more and 15 mass% or less, or 5 mass% or more and 10 mass% or less.
[0016] Here, when the metal compound-containing material is a tantalic acid hydroxide, the tantalum content in the metal compound-containing material is calculated by diluting the metal compound-containing material appropriately with dilute hydrochloric acid as necessary, and measuring the tantalum mass fraction in tantalum equivalent using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.
[0017] The metal compound-containing material of the present invention may also contain a resin. If the metal compound-containing material contains a resin, the resin is uniformly compatible with the metal compound and acts to adhere to the carbon substrate, thereby improving the film-forming properties and adhesion to the carbon substrate.
[0018] Examples of the resin contained in the metal compound-containing material include polyolefin-based compounds and polyvinyl-based compounds.
[0019] Furthermore, the resin contained in the metal compound-containing material of the present invention may be an anionic water-soluble resin and / or a nonionic water-soluble resin. When the resin contained in the metal compound-containing material of the present invention is an anionic water-soluble resin and / or a nonionic water-soluble resin, the anionic water-soluble resin and / or the nonionic water-soluble resin is uniformly compatible with the above-mentioned metal compound and acts to adhere to the substrate, thereby improving the film-forming properties and adhesion to the plastic film substrate.
[0020] Here, the cationic water-soluble resin is a resin that has a positive charge in the polymer in water of pH=7, and has a functional group of, for example, any one of amino group, imino group, tertiary amine group, quaternary ammonium group, and hydrazino group. The anionic water-soluble resin is a resin that has a negative charge in the polymer in water of pH=7, and has a functional group of, for example, any one of carboxyl group, sulfone group, sulfate ester group, and phosphate ester group. Furthermore, the nonionic water-soluble resin is a resin that does not fall under the above-mentioned cationic water-soluble resin or anionic water-soluble resin, and has a functional group of, for example, any one of hydroxyl group, ether group, and amide group in the polymer.
[0021] Furthermore, these resins may contain one or more water-soluble homopolymers selected from the group consisting of acrylic polymers, urethane polymers, styrene polymers, olefin polymers, amide polymers, siloxane polymers, epoxy polymers, vinyl chloride polymers, and vinyl acetate polymers, and / or water-soluble copolymers consisting of two or more of these polymers. In particular, it is preferable that the resins contain one or more water-soluble homopolymers of acrylic polymers, styrene polymers, and olefin polymers, and / or water-soluble copolymers consisting of two or more of these polymers.
[0022] Furthermore, the metal compound-containing material of the present invention may have a resin content of 0.1% by mass or more and 60% by mass or less when the metal compound-containing material is taken as 100% by mass. The resin content in the metal compound-containing material of the present invention is preferably 0.1% by mass or more and 60% by mass or less, since it is possible to suppress aggregation of fine metal compounds after drying and to improve the wettability of the metal compound-containing material to the carbon substrate. The resin content may be 0.15% by mass or more and 40% by mass or less, 0.2% by mass or more and 30% by mass or less, or 0.25% by mass or more and 20% by mass or less.
[0023] Furthermore, the metal compound-containing material of the present invention may contain, as a surfactant, at least one surfactant selected from the group consisting of nonionic surfactants, cationic surfactants, and anionic surfactants. Examples of the surfactant include olefin resins having an amine group, a carboxyl group, a hydroxyl group, a phosphoric acid group, a sulfone group or an unsaturated fatty acid as a functional group on the side chain, acetylene glycol compounds, polyoxyalkylenes, polyoxyethylenes, polyoxypropylenes, and the like.
[0024] Furthermore, the metal compound-containing material of the present invention may have a surfactant content of 0.001% by mass or more and 10% by mass or less when the metal compound-containing material is taken as 100% by mass. The resin content in the metal compound-containing material of the present invention is preferably 0.001% by mass or more and 10% by mass or less, since the wettability of the metal compound-containing material to the substrate can be improved. The resin content may be 0.01% by mass or more and 5% by mass or less, 0.05% by mass or more and 3% by mass or less, or 0.1% by mass or more and 1% by mass or less.
[0025] The metal compound-containing material of the present invention may also contain a carbon material. If the metal compound-containing material contains a carbon material, the carbon material becomes a carbon component during carbonization, which is preferable in that carbonization is improved.
[0026] The metal compound-containing material of the present invention may contain, as a solvent, at least one high-boiling point solvent selected from the group consisting of polyhydric alcohol solvents and glycol solvents. When the high-boiling point solvent contained in the metal compound-containing material of the present invention contains at least one solvent selected from the group consisting of polyhydric alcohol-based solvents and glycol-based solvents, the drying property of the metal compound-containing material is appropriately suppressed, thereby preventing nozzle clogging due to solids produced by drying.
[0027] Here, examples of polyhydric alcohol solvents include glycerin (boiling point: 290°C), 1,6-hexanediol (boiling point: 250°C), and 1,7-heptanediol (boiling point: 259°C). Examples of glycol solvents include ethylene glycol (boiling point: 197.3°C), propylene glycol (boiling point: 188.2°C), diethylene glycol (boiling point: 244.3°C), triethylene glycol (boiling point: 287.4°C), oligoethylene glycol (boiling point: 287°C to 460°C), polyethylene glycol (PEG) (boiling point: 460°C or higher), polyethylene glycol (PEG)-polypropylene glycol (PPG) copolymer (boiling point: 460°C). or higher), diethylene glycol monohexyl ether (boiling point: 260°C), polyoxyalkylene monoalkyl ether (boiling point: 260°C or higher), polyoxyethylene sorbitan monolaurate (boiling point: 321°C or higher), other anionic fluorosurfactants (boiling point: 180°C or higher), amphoteric fluorosurfactants (boiling point: 180°C or higher), nonionic fluorosurfactants (boiling point: 180°C or higher), amine oxides (boiling point: 180°C or higher), etc. The above boiling points are those at 1 atmospheric pressure.
[0028] In addition, since a high boiling point solvent has a high boiling point, if the boiling point at 1 atmospheric pressure is excessively high, the high boiling point solvent may decompose before boiling, making it impossible to measure the boiling point accurately. In such a case, the boiling point at reduced pressure may be measured and converted to the boiling point at 1 atmospheric pressure using a general-purpose boiling point conversion table.
[0029] Furthermore, the metal compound-containing material of the present invention may be a solution, a sol, or a gel. The metal compound-containing material is one that contains a metal compound, and more specifically, one that is liquefied by applying a shear stress. In other words, the metal compound-containing material includes those that are normally in a liquid, sol, gel, or semi-solid state, and is one that can be applied to a carbon substrate. Furthermore, the gel may have a viscosity of 200 mPa·s or more at 25°C as measured by a rotating cylinder method.
[0030] In addition, when the metal compound-containing material of the present invention is a solution, it can be easily applied to a carbon substrate, which is preferable. Furthermore, when the metal compound-containing material of the present invention contains water as a solvent, it is preferable from the viewpoint of reducing the environmental load.
[0031] The metal compound-containing material of the present invention is characterized in that the maximum light transmittance in the wavelength region of 500 nm to 700 nm is 70%T or more. In the metal compound-containing material of the present invention, the maximum light transmittance in the wavelength region of 500 nm to 700 nm is preferably 70%T or more, since the degree of dispersion is high and the uniformity of the liquid components is excellent. The maximum light transmittance in the wavelength region of 500 nm to 700 nm is more preferably 72%T or more, even more preferably 74%T or more, particularly preferably 76%T or more, particularly preferably 78%T or more, and even more particularly preferably 80%T or more. The light transmittance in the wavelength region of 500 nm to 700 nm may be 80%T. Note that, due to measurement errors, etc., the measured value of the light transmittance may exceed 100%T, but since the theoretical upper limit is 100%T, when the measured value exceeds 100%T, it is regarded as 100%T. Note that, in this specification, "light transmittance" does not specify either "initial light transmittance" or "aged light transmittance" unless otherwise specified as described later.
[0032] Furthermore, the metal compound-containing material of the present invention preferably has a light transmittance in the wavelength region of 550 nm to 700 nm of 70% T or more, more preferably 75% T or more, even more preferably 80% T or more, particularly preferably 85% T or more, more preferably 90% T or more, even more preferably 95% T or more, particularly preferably 98% T or more, even more preferably 99% T or more, and most preferably 100% T or more. Note that if the measured value exceeds 100% T due to measurement error of the spectrophotometer used to measure the light transmittance, it is considered to be 100% T.
[0033] Here, the light transmittance in the wavelength region of 500 nm to 700 nm is measured for the metal compound-containing material of the present invention using a spectrophotometer in accordance with the following light transmittance measurement conditions.
[0034] =Light transmittance measurement conditions= Measurement equipment: UV-Vis-NIR spectrophotometer UH4150 (manufactured by Hitachi High-Tech Science Corporation) Measurement mode: Wavelength scan Data mode: %T (transparent) Measurement wavelength range: 200nm~2000nm Scan speed: 600nm / min Sampling interval: 2nm
[0035] On the other hand, when the metal compound-containing material of the present invention contains a Si compound, the light transmittance in the wavelength region of 500 nm to 700 nm can be determined by placing 3 g of the metal compound-containing material of the present invention containing a Si compound adjusted to room temperature (25°C) in a measurement cell (light path length 1 cm) and measuring the ultraviolet-visible absorption spectrum (UV-Vis absorption spectrum) in accordance with the following light transmittance measurement conditions (including Si) in accordance with JIS K 0115, 2004 "General rules for spectrophotometric analysis methods".
[0036] =Light transmittance measurement conditions (including Si)= Measurement device: U-2900 spectrophotometer (Hitachi High-Tech Corporation) Measurement mode: Wavelength scan Data mode: %T (transparent) Measurement wavelength range: 200nm~1000nm Scan speed: 200nm / min Sampling interval: 1nm Cell length: 10mm Measurement cell: Disposable square cell for particle size (manufactured by Otsuka Electronics Co., Ltd.)
[0037] The metal compound-containing material of the present invention is also characterized in that the particle diameter (D50) of the particles in the metal compound-containing material measured by dynamic light scattering is 3000 nm or less. The particle diameter (D50) of the particles in the metal compound-containing material of the present invention is preferably 3000 nm or less from the viewpoint of stability over time, more preferably 2000 nm or less, and may be 1000 nm or less, 500 nm or less, 400 nm or less, 300 nm or less, 100 nm or less, 50 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 5 nm or less, 3 nm or less, or 2 nm or less. On the other hand, the particle diameter (D50) is preferably 0.1 nm or more, more preferably 0.5 nm or more, even more preferably 0.7 nm or more, and particularly preferably 1 nm or more. Typically, the particle diameter (D50) is 0.6 nm or more and 200 nm or less. In this specification, the "particle diameter (D50)" does not specify either "initial particle diameter (D50)" or "aged particle diameter (D50)" as described later, unless otherwise specified.
[0038] Here, the dynamic light scattering method is a method in which a solution such as a suspension is irradiated with light such as a laser beam to measure the light scattering intensity from a group of particles undergoing Brownian motion, and the particle size and distribution are obtained from the temporal variation of the intensity. Specifically, the particle size distribution is evaluated using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000ZS) in accordance with JIS Z 8828:2019 "Particle size analysis - dynamic light scattering method". In addition, if necessary, the measurement sample is diluted 1000 times with pure water, and the measurement sample is filtered with a filter with a pore size of 11 μm to remove dust and the like in the measurement sample immediately before measurement, and ultrasonic treatment is performed for 3 minutes with an ultrasonic cleaner (manufactured by As One Co., Ltd.: VS-100III). In addition, the liquid temperature of the measurement sample was adjusted to 25 °C. The particle size (D50) refers to the median diameter (D50), which is the particle size that shows the 50% cumulative value of the cumulative distribution curve.
[0039] The metal compound-containing material of the present invention is also characterized by having a pH of 6.5 or more and 13.5 or less. The pH of the metal compound-containing material of the present invention is preferably 6.5 or more in terms of good solubility. The pH of the metal compound-containing material is more preferably 7.0 or more, even more preferably 7.5 or more, and particularly preferably 8.0 or more. The pH of the metal compound-containing material may be 8.5 or more, 9.0 or more, 9.5 or more, 10.0 or more, 10.5 or more, or 11.0 or more. On the other hand, the pH of the metal compound-containing material is preferably 13.5 or less, more preferably 13.0 or less, and even more preferably 12.5 or less. In this specification, "pH" does not specify either "initial pH" or "time-dependent pH" unless otherwise specified as described later.
[0040] Here, the pH of the metal compound-containing material of the present invention is measured by immersing an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) in the metal compound-containing material and confirming that the liquid temperature has stabilized at 25°C.
[0041] The metal compound-containing material of the present invention may also contain ammonia. The metal compound-containing material of the present invention is produced by a reverse neutralization method in which an acidic metal acid solution is added to ammonia water during the manufacturing process of the metal compound-containing material of the present invention, and therefore it is believed that ammonia containing ammonium ions is present in the material as cations.
[0042] Methods for measuring the ammonia concentration in the inclusions include adding sodium hydroxide to the inclusions to separate the ammonia by distillation and quantifying the ammonia concentration using an ion meter, quantifying the N2 content in a gasified sample using a thermal conductivity meter, the Kjeldahl method, gas chromatography (GC), ion chromatography, gas chromatography-mass spectrometry (GC-MS), etc. In particular, the quantitative method using an ion meter is preferred.
[0043] The ammonia concentration of the ammonia containing ammonium ions contained in the metal compound-containing material of the present invention is preferably 0.001% by mass to 25% by mass, more preferably 0.003% by mass to 15% by mass. The ammonia concentration may be 0.1% by mass to 10% by mass, 0.5% by mass to 10% by mass, or 1% by mass to 8% by mass.
[0044] The metal compound-containing material of the present invention may also contain an organic nitrogen compound and / or hydrogen peroxide. Since the metal compound contained in the metal compound-containing material of the present invention is produced using an organic nitrogen compound and / or aqueous hydrogen peroxide in its manufacturing method, the metal compound-containing material of the present invention may contain an organic nitrogen compound and / or hydrogen peroxide.
[0045] It is presumed that the organic nitrogen compound in the metal compound-containing composition of the present invention is present in the composition as an ion in an ionic state with the metal compound.
[0046] Examples of the organic nitrogen compound include aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium, guanidine compounds, and azole compounds.
[0047] Examples of aliphatic amines include methylamine, dimethylamine, trimethylamine, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, tert-butylamine, n-pentamine, n-hexylamine, cyclohexylamine, piperidine, and the like.
[0048] Examples of aromatic amines include aniline, phenylenediamine, and diaminotoluene. Examples of amino alcohols include methanolamine, ethanolamine, propanolamine, butanolamine, pentanolamine, dimethanolamine, diethanolamine, trimethanolamine, methylmethanolamine, methylethanolamine, methylpropanolamine, methylbutanolamine, ethylmethanolamine, ethylethanolamine, ethylpropanolamine, dimethylmethanolamine, dimethylethanolamine, dimethylpropanolamine, methyldimethanolamine, methyldiethanolamine, diethylmethanolamine, trishydroxymethylaminomethane, bis(2-hydroxyethyl)aminotris(hydroxymethyl)methane, and aminophenol. Examples of amino acids include alanine, arginine, aspartic acid, and EDTA. Examples of polyamines include polyamines and polyetheramines.
[0049] Examples of quaternary ammonium include alkylimidazolium, pyridinium, pyrrolidium, tetraalkylammonium, etc. Specific examples of alkylimidazolium include 1-methyl-3-methylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1-methyl-2,3-dimethylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-propyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, etc. Specific examples of pyridinium and pyrrolidium include N-butyl-pyridinium, N-ethyl-3-methyl-pyridinium, N-butyl-3-methyl-pyridinium, N-hexyl-4-(dimethylamino)-pyridinium, N-methyl-1-methylpyrrolidinium, and N-butyl-1-methylpyrrolidinium. Specific examples of tetraalkylammonium include tetramethylammonium, tetraethylammonium, tetrabutylammonium, ethyl-dimethyl-propylammonium, and choline. Examples of anions that form salts with the above-mentioned cations include OH, - , Cl - , Br - , I - , BF4 - , HSO4 - etc.
[0050] Examples of the guanidine compound include guanidine, diphenylguanidine, and ditolylguanidine. Examples of the azole compound include imidazole compounds and triazole compounds. Specific examples of the imidazole compound include imidazole, 2-methylimidazole, and 2-ethyl-4-methylimidazole. Specific examples of the triazole compound include 1,2,4-triazole, 1,2,4-triazole-3-methyl carboxylate, and 1,2,3-benzotriazole.
[0051] Here, the organic nitrogen compound is preferably an aliphatic amine because it is highly volatile and has low toxicity. Specifically, an aliphatic amine having 1 to 6 carbon atoms is more preferable, an aliphatic amine having 1 to 4 carbon atoms is even more preferable, and an aliphatic amine having 1 to 2 carbon atoms is particularly preferable. Examples of the organic nitrogen compound include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, and isopropylamine.
[0052] In addition, the organic nitrogen compound is preferably a quaternary ammonium, since it has high solubility and high crystallization inhibition and high sol formation inhibition. For example, tetraalkylammonium salts are preferred, tetraalkylammonium hydroxide salts are more preferred, tetramethylammonium hydroxide and tetraethylammonium are particularly preferred, and tetramethylammonium hydroxide (TMAH) is also particularly preferred.
[0053] Furthermore, the organic nitrogen compound may be a mixture of two or more selected from aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium, guanidine compounds, and azole compounds, rather than one selected from them. For example, a mixture of two types of compounds, an aliphatic amine and a quaternary ammonium compound, is preferable in that the amount of the compound added is reduced so as not to increase toxicity, while the solubility can be increased.
[0054] Specifically, examples of such mixtures include mixtures of two organic nitrogen compounds, such as methylamine and tetramethylammonium hydroxide (TMAH), dimethylamine and tetramethylammonium hydroxide (TMAH), and methylamine and dimethylamine, and mixtures of three organic nitrogen compounds, such as methylamine, dimethylamine, and tetramethylammonium hydroxide (TMAH).
[0055] The method for measuring the concentration of the organic nitrogen compound present in the metal compound-containing material of the present invention includes gas chromatography (GC), liquid chromatography (LC), mass spectrometry (MS), gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), etc. In particular, measurement by liquid chromatography (LC) or liquid chromatography-mass spectrometry (LC-MS) is preferred.
[0056] As described above, the organic nitrogen compound contained in the metal compound-containing material of the present invention is preferably an aliphatic amine such as methylamine, dimethylamine, ethylamine, trimethylamine, or a mixture thereof, or a quaternary ammonium compound such as tetramethylammonium hydroxide (TMAH) or tetraethylammonium hydroxide (TEAH).
[0057] The method for detecting hydrogen peroxide in a metal compound-containing material of the present invention can confirm the content of hydrogen peroxide in the material by measuring the relative intensity of absorbance with a standard solution of hydrogen peroxide, for example, using a standard addition method. Specifically, a wavelength region in which a change in absorbance due to the formation of a peroxo complex is observed is found from the UV-visible absorption spectrum of a standard solution containing hydrogen peroxide at a known concentration, for example, 1% by mass, and a standard solution to which hydrogen peroxide is not added, and if the difference in absorbance between the standard solution to which hydrogen peroxide is not added and a sample with an unknown hydrogen peroxide concentration in that wavelength region is less than 1%, it can be confirmed that the sample with an unknown hydrogen peroxide concentration does not substantially contain hydrogen peroxide. When hydrogen peroxide is contained in the material, hydrogen peroxide reacts with a metal polyacid to form a peroxo complex, so that the absence of hydrogen peroxide in the material can be confirmed by confirming the difference in absorbance with the standard solution to which hydrogen peroxide is not added, as described above. In addition to the above-mentioned standard addition method, for example, a commercially available hydrogen peroxide measurement kit may be used to add a reagent that undergoes a color reaction with hydrogen peroxide to the substance and measure the color development, or a reagent that undergoes a fluorescent reaction with hydrogen peroxide to the substance and measure the light emission, thereby performing qualitative and quantitative analysis of hydrogen peroxide in the substance.
[0058] The carbon substrate of the present invention may be a substrate made of only carbon, a substrate mainly made of carbon with a carbon content of 50% by mass or more, or a substrate having a multi-layer structure with the outermost layer made of only carbon or mainly made of carbon with a carbon content of 50% by mass or more. It is particularly preferable that the carbon substrate is a substrate made of only carbon.
[0059] The size and shape of the carbon substrate are not particularly limited as long as they can be heated in a stationary furnace used in the heating step described below.Specific examples of the carbon substrate include crucibles, furnace materials, electrodes, fibers, filtration devices, filters, protective tubes, heater tubes, burner nozzles, and fire-resistant jigs.
[0060] Examples of the carbon material of the carbon substrate include fullerene, carbon nanotube, carbon nanofiber, graphene, graphene oxide, carbon nanohorn, diamond, hyper diamond, and carbon fiber.
[0061] The carbon material may be made of only carbon or may be made of other materials containing carbon. The carbon material may have a uniform structure or a non-uniform structure. The uniform structure may be hollow or porous. The non-uniform structure may be, for example, an island-in-the-sea structure, a multi-layer structure, a hollow structure, or a porous structure.
[0062] Furthermore, the carbon material may be in the form of a powder, a plate, a film, a fiber, or the like, and may be in the form of a molded product thereof, i.e., a mixture, a multilayer body, a pressed powder body, a sintered body, a fiber bundle body, a nonwoven body, or a woven material (plain weave, twill weave, satin weave, basket weave).
[0063] The carbon material is particularly preferably a fibrous material, and specific examples thereof include metal fibers (such as steel fibers), ceramic fibers (such as metal oxide fibers, metal carbide fibers, metal nitride fibers, silicon carbide fibers, and glass fibers), and polymer fibers (such as natural polymer fibers, polysaccharide fibers, cellulose fibers, artificial polymer fibers, resin fibers, and carbon fibers).
[0064] Furthermore, the metal compound-containing material of the present invention may contain components (referred to as "other components") other than the components derived from the metal compound, within a range that does not impair the action and effect of the metal compound-containing material. Examples of other components include Li, Mg, Si, Ca, Ti, Mn, Ni, Cu, Zn, Sr, Zr, Mo, Ba, W, Bi, and B. However, the other components are not limited to these. The content of other components in the metal compound-containing material is preferably less than 5 mass%, more preferably less than 4 mass%, and even more preferably less than 3 mass%. It is assumed that the metal compound-containing material contains unavoidable impurities, not intentionally. The content of unavoidable impurities is preferably less than 0.01 mass%.
[0065] As an example of the method for producing the above-mentioned metal compound-containing material of the present invention, a method for producing a titanic acid-containing liquid will be described below.
[0066] The method for producing a titanic acid-containing liquid includes a neutralization step of mixing a titanium salt solution with an aqueous amine solution to obtain a neutralized reaction liquid, a washing step of washing a titanium-containing precipitate produced in the neutralized reaction liquid, and a dissolution step of mixing the washed titanium-containing precipitate with a quaternary ammonium salt and water to obtain a titanic acid-containing liquid.
[0067] The titanium salt solution may be any solution in which titanium is dissolved. Examples include an aqueous titanyl sulfate solution, an aqueous titanium chloride solution, and an aqueous titanium fluoride solution. The aqueous titanium chloride solution is produced by dissolving titanium chloride (TiCl5) in a small amount of methanol and adding water. The aqueous titanyl sulfate solution is produced by dissolving titanyl sulfate in hot water. The titanium content in the aqueous titanyl sulfate solution is preferably adjusted to 8 to 15 mass% in terms of TiO2.
[0068] In the neutralization step, the titanium salt solution and the amine aqueous solution are mixed and reacted to obtain a neutralized reaction solution. In the neutralization step, it is preferable to carry out reverse neutralization by adding a titanium salt solution such as a titanyl sulfate aqueous solution to the amine aqueous solution to react with each other. It is presumed that the structure of titanium or titanic acid becomes easily soluble in water by reverse neutralization in this manner.
[0069] The amine in the aqueous amine solution used in the neutralization step is preferably an alkylamine. The alkylamine preferably has 1 to 3 alkyl groups. When the alkylamine has 2 to 3 alkyl groups, the three alkyl groups may all be the same or may include different alkyl groups. From the viewpoint of solubility, the alkyl group of the alkylamine preferably has 1 to 6 carbon atoms, more preferably 4 or less, even more preferably 3 or less, and particularly preferably 2 or less.
[0070] Specific examples of alkylamines include methylamine, dimethylamine, trimethylamine, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, tert-butylamine, n-pentaamine, n-hexaamine, etc. In particular, from the viewpoint of solubility, methylamine, dimethylamine, trimethylamine, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, and dimethylethylamine are preferred, and methylamine, dimethylamine, and trimethylamine are more preferred.
[0071] In the neutralization step, from the viewpoint of enhancing dispersibility, the titanium salt solution is preferably added to an aqueous amine solution containing an amine in an amount equal to or greater than the molar ratio of sulfuric acid contained in the titanium salt solution, i.e., an amount equal to or greater than 1, more preferably an amount equal to or greater than 1.2, and even more preferably an amount equal to or greater than 1.4. On the other hand, from the viewpoint of increasing the amount of waste liquid, the titanium salt solution is preferably added to an aqueous amine solution containing an amine in a molar ratio of 2 or less to the molar ratio of sulfuric acid contained in the titanium salt solution, more preferably an amount equal to or less than 1.8, and even more preferably an amount equal to or less than 1.6.
[0072] Furthermore, in the neutralization step, when a titanium salt solution such as an aqueous titanyl sulfate solution is added to the aqueous amine solution, it is preferable to carry out the neutralization reaction within 1 minute. That is, it is preferable to add the titanium salt solution within 1 minute, for example, all at once, rather than gradually adding the titanium salt solution over a period of time, to carry out the neutralization reaction. In this case, the addition time of the titanium salt solution is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds.
[0073] Next, the washing method in the washing step may be, for example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, as well as centrifugation and other known methods. Note that the washing step may be performed at room temperature, and there is no particular need to adjust the temperature of each step.
[0074] The neutralization reaction liquid obtained in the above-mentioned neutralization step, and particularly the titanium-containing precipitate, contains unnecessary components other than titanium or titanic acid hydrates or ions and amines, such as sulfate compounds such as ammonium sulfate, as impurities in the water, and therefore it is preferable to wash away the unnecessary components.
[0075] In the dissolution process, a dispersion medium such as water is added to the titanium-containing precipitate obtained by washing in the washing process, for example, the titanium-containing precipitate obtained by removing sulfuric acid, and a quaternary ammonium salt is added, and the mixture is stirred as necessary to obtain a titanic acid-containing liquid.
[0076] Here, examples of the quaternary ammonium salt include tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, methyltripropylammonium hydroxide, methyltributylammonium hydroxide, tetrapentylammonium hydroxide, tetrahexylammonium hydroxide, ethyltrimethylammonium hydroxide, dimethyldiethylammonium hydroxide, benzyltrimethylammonium hydroxide, hexadecyltrimethylammonium hydroxide, and (2-hydroxyethyl)trimethylammonium hydroxide. Note that when primary to tertiary amines or salts thereof are added instead of the above-mentioned quaternary ammonium salt, it is not possible to form an aqueous solution.
[0077] As described above, the amount of quaternary ammonium salt added is preferably such that a quaternary ammonium salt containing 0.44 mol or more of quaternary ammonium is mixed per mol of titanium contained in the titanium-containing precipitate after washing, since a larger amount of quaternary ammonium can increase the solubility of titanium or titanic acid in water, in the dissolving step. On the other hand, if the amount of quaternary ammonium is too large, problems such as impeding film-forming properties or inhibiting catalytic action may occur, so that a quaternary ammonium salt having 1.0 mol or less of quaternary ammonium is mixed per mol of titanium contained in the titanium-containing precipitate after washing, in the dissolving step.
[0078] As another example of the method for producing a metal compound-containing material of the present invention, a method for producing a niobic acid-containing liquid will be described below.
[0079] The method for producing a niobic acid-containing liquid includes a step of producing an acidic niobium solution containing niobium, a step of obtaining a precipitate slurry containing niobium by a reverse neutralization method in which the acidic niobium solution is added to ammonia water, and a step of mixing the obtained precipitate slurry containing niobium with at least one selected from an amine and ammonia, and stirring the mixture to obtain a niobic acid-containing liquid.
[0080] In the step of producing an acidic niobium solution containing niobium, the acidic niobium solution refers to an acidic niobium solution containing fluoride ions obtained by solvent extraction of a solution in which niobium is dissolved in an acidic solution containing hydrofluoric acid.
[0081] Here, it is preferable to adjust the acidic niobium solution containing fluoride ions, for example, the niobium fluoride aqueous solution, to contain niobium at 1 to 100 g / L in terms of Nb2O5 by adding water (for example, pure water). In this case, it is preferable that the niobium concentration is 1 g / L or more in terms of Nb2O5, since it becomes a niobium acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the niobium concentration is 100 g / L or less in terms of Nb2O5, since it becomes a niobium acid compound hydrate that is easily soluble in water, and in order to synthesize a niobium acid compound hydrate that is easily soluble in water more reliably, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the niobium fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving niobium or niobium oxide.
[0082] Next, in the step of obtaining a precipitation slurry containing niobium by a reverse neutralization method in which the acidic niobium solution is added to ammonia water (hereinafter referred to as a reverse neutralization step), it is preferable to obtain a precipitation slurry containing niobium by adding an acidic niobium solution containing fluoride ions to ammonia water of a predetermined concentration, i.e., by the reverse neutralization method.
[0083] The ammonia concentration of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, niobium is less likely to remain undissolved, and niobium or niobic acid can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.
[0084] From this viewpoint, the ammonia concentration of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0085] In the reverse neutralization step, the amount of niobium fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / Nb2O5 is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. In addition, the amount of niobium fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more, from the viewpoint of generating amines or niobic acid compounds that dissolve in dilute ammonia water. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or more, and even more preferably 40 or more.
[0086] In the reverse neutralization step, the time for adding the niobium fluoride aqueous solution to the ammonia water is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds. That is, it is preferable to add the niobium fluoride aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the niobium fluoride aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, in the reverse neutralization step, since the acidic niobium fluoride aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The niobium fluoride aqueous solution and the ammonia water can be used at room temperature.
[0087] The method for producing a niobium acid-containing liquid also includes a step of removing fluoride ions from a niobium-containing precipitate slurry obtained by the reverse neutralization method to obtain a niobium-containing precipitate from which fluoride ions have been removed. The niobium-containing precipitate slurry obtained by the reverse neutralization method contains fluorine compounds such as ammonium fluoride as impurities, and it is therefore preferable to remove these.
[0088] Any method can be used to remove the fluorine compounds, and examples of such methods include filtration using a membrane such as reverse osmosis filtration, ultrafiltration, and microfiltration using aqueous ammonia or pure water, centrifugation, and other known methods. When removing fluoride ions from the niobium-containing precipitate slurry, temperature control is not particularly required, and the removal may be performed at room temperature.
[0089] Specifically, the niobium-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby obtaining a niobium-containing precipitate from which the fluoride ions have been removed.
[0090] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water of 5.0 mass% or less is preferable, ammonia water of 4.0 mass% or less is more preferable, ammonia water of 3.0 mass% or less is even more preferable, and ammonia water of 2.5 mass% is particularly preferable. When the ammonia water is 5.0 mass% or less, ammonia containing ammonium ions is suitable for fluoride ions, and unnecessary cost increase can be avoided.
[0091] The niobium-containing precipitate thus obtained, from which the fluoride ions have been removed, is diluted with pure water or the like to obtain a precipitate slurry containing niobium from which the fluoride ions have been removed. The niobium concentration of the precipitate slurry containing niobium is measured by taking a portion of the slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce Nb2O5. The weight of the Nb2O5 thus produced can be measured, and the niobium concentration of the slurry can be calculated from the weight.
[0092] The precipitate slurry containing niobium from which the fluoride ions have been removed is mixed with at least one selected from amines and ammonia, and the resulting mixture is stirred to obtain a niobic acid-containing liquid.
[0093] At least one selected from the group consisting of amines and ammonia mixed with the niobium-containing precipitation slurry is selected from the group consisting of alkylamines, choline ([(CH3)3NCH2CH2OH] + ), choline hydroxide ([(CH3)3NCH2CH2OH] + OH - ) is preferred.
[0094] The alkylamine preferably has 1 to 4 alkyl groups. When the alkylamine has 2 to 4 alkyl groups, the 2 to 4 alkyl groups may all be the same or may include different alkyl groups. From the viewpoint of solubility, the alkyl group of the alkylamine preferably has 1 to 6 carbon atoms, more preferably 4 or less, even more preferably 3 or less, and particularly preferably 2 or less.
[0095] Specific examples of alkylamines include methylamine, dimethylamine, trimethylamine, tetramethylammonium hydroxide, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, tetraethylammonium hydroxide, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, tert-butylamine, n-pentamine, n-hexamine, etc. In particular, from the viewpoint of solubility, methylamine, dimethylamine, trimethylamine, tetramethylammonium hydroxide, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, and tetraethylammonium hydroxide are more preferable, methylamine, dimethylamine, trimethylamine, and tetramethylammonium hydroxide are further preferable, and methylamine is particularly preferable.
[0096] As another example of the metal compound-containing material of the present invention, a method for producing a molybdic acid-containing liquid will be described below.
[0097] The method for producing a molybdic acid-containing liquid is characterized by comprising the steps of: adding an acidic molybdenum aqueous solution containing 1 to 100 g / L of molybdenum calculated as MoO3 to a 10 to 30 mass % ammonia aqueous solution to produce a molybdenum-containing precipitate; and adding an organic nitrogen compound to the molybdenum-containing precipitate slurry obtained by turning the molybdenum-containing precipitate into a slurry to produce a molybdic acid-containing liquid.
[0098] First, in the step of adding an acidic molybdenum aqueous solution containing 1 to 100 g / L of molybdenum calculated as MoO3 to a 10 to 30 mass % ammonia aqueous solution to generate a molybdenum-containing precipitate, the acidic molybdenum aqueous solution refers to an aqueous molybdenum sulfate solution obtained by solvent extraction of a solution in which molybdenum is dissolved in an acidic aqueous solution containing sulfuric acid. Note that, unless otherwise specified, molybdenum referred to in this specification includes molybdenum oxide.
[0099] Here, it is preferable to adjust the molybdenum sulfate aqueous solution to contain 1 to 100 g / L of molybdenum in terms of MoO3 by adding water (e.g., pure water). In this case, it is preferable that the molybdenum concentration is 1 g / L or more in terms of MoO3, since it becomes a molybdic acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the molybdenum concentration is 100 g / L or less in terms of MoO3, since it becomes a molybdic acid compound hydrate that is easily soluble in water, and in order to synthesize a molybdic acid compound hydrate that is easily soluble in water more reliably, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the molybdenum sulfate aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving molybdenum or molybdenum oxide.
[0100] When the aqueous molybdenum sulfate solution is added to the aqueous ammonia solution, in the so-called reverse neutralization method, it is preferable to add the aqueous molybdenum sulfate solution to a 10% by mass to 30% by mass aqueous ammonia solution, i.e., to obtain a slurry of a molybdic acid compound hydrate, that is, a slurry of a molybdenum-containing precipitate, by the reverse neutralization method.
[0101] The ammonia concentration of the aqueous ammonia solution used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, molybdenum is less likely to remain undissolved, and molybdenum or molybdenum oxide can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous ammonia solution.
[0102] From this viewpoint, the ammonia concentration of the aqueous ammonia solution is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0103] In the reverse neutralization, the amount of molybdenum sulfate aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / MoO3 is 0.1 or more and 300 or less, more preferably 5 or more and 200 or less. In addition, the molybdenum sulfate aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / SO4 2- The molar ratio of NH3 / SO4 is preferably 3.0 or more, more preferably 10.0 or more, and even more preferably 20.0 or more. On the other hand, from the viewpoint of cost reduction, the NH3 / SO4 2- The molar ratio of is preferably 200 or less, more preferably 150 or less, and even more preferably 100 or less.
[0104] In the reverse neutralization, the time for adding the molybdenum sulfate aqueous solution to the ammonia water is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds. That is, rather than gradually adding the molybdenum sulfate aqueous solution over a period of time, it is preferable to add it to the ammonia water in as short a time as possible, for example, all at once, and carry out the neutralization reaction. In addition, in the reverse neutralization, since the acidic molybdenum sulfate aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The molybdenum sulfate aqueous solution and the ammonia water can be used at room temperature.
[0105] The molybdenum-containing precipitate slurry obtained by the reverse neutralization method is then subjected to sulfur removal to produce a molybdenum-containing precipitate from which the sulfur has been removed. Since the molybdenum-containing precipitate slurry obtained by the reverse neutralization method contains, as impurities, sulfate ions that remain without reacting with molybdenum or molybdenum oxide and sulfur in the form of hydrogen sulfate ions, it is preferable to remove these.
[0106] Any method for removing sulfur may be used, and examples of the method include a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, centrifugation, and other known methods. When removing sulfur from the slurry of the molybdenum-containing precipitate, temperature control is not particularly required, and the removal may be performed at room temperature.
[0107] Specifically, the molybdenum-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the conductivity of the molybdenum-containing precipitate slurry becomes 500 μS / cm or less, thereby obtaining a molybdenum-containing precipitate from which sulfur has been removed. The conductivity was measured by adjusting the liquid temperature of the molybdenum-containing precipitate slurry to 25° C., immersing the measuring part of a conductivity meter (ASCON2 manufactured by AS ONE CORPORATION) in the supernatant liquid of the precipitate slurry, and reading the conductivity value after it stabilized.
[0108] The cleaning solution used to remove the sulfur content is preferably ammonia water. Specifically, ammonia water of 5.0 mass% or less is preferable, ammonia water of 4.0 mass% or less is more preferable, ammonia water of 3.0 mass% or less is even more preferable, and ammonia water of 2.5 mass% is particularly preferable. When the ammonia water is 5.0 mass% or less, ammonia and ammonium ions are appropriate for the sulfur content, and unnecessary cost increases can be avoided.
[0109] Next, in the step of adding an organic nitrogen compound to the molybdenum-containing precipitate slurry obtained by slurriing the molybdenum-containing precipitate to produce a molybdic acid-containing liquid, the molybdenum-containing precipitate slurry is obtained by diluting the molybdenum-containing precipitate from which sulfur has been removed with pure water or the like as described above. The molybdenum concentration of the molybdenum-containing precipitate slurry from which sulfur has been removed is measured by taking a portion of the slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce MoO3. The weight of the MoO3 thus produced can be measured, and the molybdenum concentration of the slurry can be calculated from the weight.
[0110] Then, by mixing an organic nitrogen compound with the molybdenum-containing precipitate slurry from which the sulfur content has been removed, a molybdic acid-containing liquid is obtained.
[0111] Specifically, the obtained molybdenum-containing precipitate slurry is added to an organic nitrogen compound and mixed with pure water so that the molybdenum concentration in the final mixture is 0.1 to 40 mass% in terms of MoO3, and the mixture is stirred while maintaining the liquid temperature at room temperature (25°C) for 1 hour, thereby obtaining a colorless and transparent molybdic acid-containing liquid.
[0112] The organic nitrogen compounds which are mixed with the molybdenum-containing precipitation slurry are preferably aliphatic amines and / or quaternary ammonium compounds.
[0113] Here, from the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the molybdenum-containing precipitation slurry is 40 mass% or less. From the same viewpoint, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the molybdenum-containing precipitation slurry is 0.1 mass% or more, more preferably 20 mass% or more. The aliphatic amine is more preferably methylamine or dimethylamine, and particularly preferably methylamine.
[0114] On the other hand, from the viewpoint of solubility, the quaternary ammonium is preferably mixed so that the quaternary ammonium concentration in the molybdenum-containing precipitation slurry is 40 mass% or less. From the same viewpoint, the quaternary ammonium is preferably mixed so that the quaternary ammonium concentration in the molybdenum-containing precipitation slurry is 0.1 mass% or more, and more preferably 20 mass% or more. The quaternary ammonium is more preferably tetramethylammonium hydroxide (TMAH).
[0115] Furthermore, the organic nitrogen compound to be mixed with the molybdenum-containing precipitation slurry may be a mixture of two or more of aliphatic amines or quaternary ammonium, rather than one of them. For example, a mixture of two or more organic nitrogen compounds such as methylamine and tetramethylammonium hydroxide (TMAH), dimethylamine and tetramethylammonium hydroxide (TMAH), or methylamine and dimethylamine, or a mixture of three or more organic nitrogen compounds such as methylamine, dimethylamine, and tetramethylammonium hydroxide (TMAH) may be used, and may be appropriately changed according to the application.
[0116] As another example of the method for producing a metal compound-containing material of the present invention, a method for producing a hafnic acid-containing liquid will be described below.
[0117] The method for producing a hafnium acid-containing liquid of the present invention is characterized by comprising the steps of: adding an acidic hafnium aqueous solution containing hafnium to an alkaline aqueous solution to produce a hafnium-containing precipitate; and adding an organic nitrogen compound to the hafnium-containing precipitate slurry obtained by turning the hafnium-containing precipitate into a slurry to produce a hafnium acid-containing liquid.
[0118] First, hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, is added to hafnium, hafnium oxide, or hafnium hydroxide, and the mixture is kept at 60°C to 100°C in a water bath for 1 to 72 hours to cause a reaction to occur, producing hafnium fluoride (HfF4). This is then dissolved in water to produce a hydrofluoric acid solution of the hafnium compound.
[0119] Here, it is preferable to adjust the hafnium compound hydrofluoric acid solution to contain 1 to 100 g / L of hafnium in terms of HfO2 by adding water (e.g., pure water). At this time, it is preferable that the hafnium concentration is 1 g / L or more in terms of HfO2, since it becomes a hafnium oxide compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the hafnium concentration is 100 g / L or less in terms of HfO2, since it becomes a hafnium oxide compound hydrate that is easily soluble in water, and in order to more reliably synthesize a hafnium oxide compound hydrate that is easily soluble in water, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. Note that the pH of the hafnium compound hydrofluoric acid solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving hafnium or hafnium oxide.
[0120] Next, hydrogen peroxide is added to the hydrofluoric acid solution of the hafnium compound and mixed to obtain an acidic or neutral aqueous hafnium complex solution. It is presumed that at least a portion of the hafnium contained in the obtained aqueous hafnium complex solution forms a peroxo complex.
[0121] Here, the hydrogen peroxide concentration of the hydrogen peroxide solution added to the hydrofluoric acid solution of the hafnium compound is preferably 0.5% by mass to 35% by mass. Also, hydrogen peroxide is preferably added so that the molar ratio H2O2 / Hf of hydrogen peroxide to hafnium is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing.
[0122] In the step of adding the hafnium complex aqueous solution to the alkaline aqueous solution to generate the hafnium-containing precipitate, the hafnium complex aqueous solution is added to the alkaline aqueous solution, for example, ammonia water, that is, a reverse neutralization method is used to obtain a precipitate slurry containing hafnium.Then, fluoride ions are removed from the obtained precipitate slurry containing hafnium, thereby obtaining a hafnium-containing precipitate from which fluoride ions have been removed.
[0123] The ammonia concentration of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, hafnium is less likely to remain undissolved, and hafnium or hafnic acid can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.
[0124] From this viewpoint, the ammonia concentration of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0125] In the reverse neutralization step, the amount of hafnium complex aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / Hf is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. In addition, the amount of hafnium complex aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more, from the viewpoint of generating hafnium acid compounds that dissolve in amines or dilute ammonia water. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.
[0126] In the reverse neutralization step, the time for adding the hafnium complex aqueous solution to the ammonia water is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to add the hafnium complex aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the hafnium complex aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, since the hafnium complex aqueous solution is added to the alkaline ammonia water in the reverse neutralization step, the neutralization reaction can be carried out while maintaining a high pH. The hafnium complex aqueous solution and the ammonia water can be used at room temperature.
[0127] In the reverse neutralization step, fluoride ions are removed from the hafnium-containing precipitate slurry obtained by the reverse neutralization method, thereby obtaining a hafnium-containing precipitate from which fluoride ions have been removed. The hafnium-containing precipitate slurry obtained by the reverse neutralization method contains fluorine compounds such as ammonium fluoride as impurities, and it is therefore preferable to remove these.
[0128] Any method can be used to remove the fluorine compounds, and for example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, centrifugation, or other known methods can be used. Note that when removing fluoride ions from the hafnium-containing precipitation slurry, there is no particular need to adjust the temperature, and the removal can be carried out at room temperature.
[0129] Specifically, the hafnium-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washed several times until the amount of liberated fluoride ions is 100 mg / L or less, thereby obtaining a hafnium-containing precipitate from which the fluoride ions have been removed. By repeating the decantation and washing several times, for example three times, the added fluoride ions are removed, and hydrogen peroxide is also removed.
[0130] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water having a concentration of 1% by mass or more and 35% by mass or less is preferable. With such ammonia water, ammonia is suitable for fluoride ions, and unnecessary cost increases can be avoided.
[0131] The hafnium-containing precipitate from which the fluoride ions have been removed is diluted with pure water or the like to obtain a hafnium-containing precipitate slurry from which the fluoride ions have been removed. The hafnium concentration of the hafnium-containing precipitate slurry is measured by taking a portion of the hafnium-containing precipitate slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce HfO2. The weight of the HfO2 produced in this manner is measured, and the hafnium concentration of the hafnium-containing precipitate slurry can be calculated from the weight.
[0132] The hafnium-containing precipitate slurry from which the fluoride ions have been removed, an organic nitrogen compound, and pure water are mixed together and stirred at 5°C to 90°C for 0.1 to 48 hours to obtain the hafnium acid-containing liquid of the present invention.
[0133] More preferably, the organic nitrogen compound mixed with the hafnium-containing precipitation slurry is a quaternary ammonium compound, as described above.
[0134] From the viewpoint of solubility, the quaternary ammonium is preferably mixed so that the quaternary ammonium concentration in the hafnium-containing precipitation slurry is 40% by mass or less, more preferably 20% by mass or less. From the same viewpoint, the quaternary ammonium is preferably mixed so that the quaternary ammonium compound concentration in the hafnium-containing precipitation slurry is 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. It is more preferable that the quaternary ammonium is one or more selected from TMAH, TEAH, choline, and benzyltrimethylammoniumhydroxy.
[0135] Furthermore, the quaternary ammonium to be mixed with the hafnium-containing precipitation slurry may be a mixture of two or more quaternary ammoniums selected from TMAH, TEAH, choline, and benzyltrimethylammonium hydroxyl, rather than one selected from these. For example, a mixture of two quaternary ammoniums such as TMAH and TEAH, TMAH and choline, or TMAH and benzyltrimethylammonium hydroxyl, a mixture of three quaternary ammoniums such as TMAH, TEAH, and choline, or a mixture of four quaternary ammoniums such as TMAH, TEAH, choline, and benzyltrimethylammonium hydroxyl, may be mentioned.
[0136] As another example of the method for producing a metal compound-containing material of the present invention, a method for producing a tantalic acid-containing liquid will be described below.
[0137] The method for producing a tantalic acid-containing liquid includes a reaction step of adding hydrogen peroxide to an aqueous tantalum fluoride solution to produce an aqueous tantalum compound solution, a reverse neutralization step of adding the aqueous tantalum compound solution to an alkaline aqueous solution to produce a tantalum-containing precipitate, and a step of mixing the produced tantalum-containing precipitate with an organic nitrogen compound.
[0138] First, the tantalum fluoride aqueous solution can be prepared by reacting tantalum, tantalum oxide, or tantalum hydroxide with hydrofluoric acid (HF) such as an aqueous solution of hydrofluoric acid to form tantalum fluoride (H2TaF7), which is then dissolved in water.
[0139] Here, it is preferable to adjust the acidic tantalum solution containing fluoride ions, for example, the tantalum fluoride aqueous solution, to contain tantalum at 1 to 100 g / L in terms of Ta2O5 by adding water (for example, pure water). In this case, it is preferable that the tantalum concentration is 1 g / L or more in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the tantalum concentration is 100 g / L or less in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tantalic acid compound hydrate that is easily soluble in water, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the tantalum fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving tantalum or tantalum oxide.
[0140] Next, in the reaction step of adding hydrogen peroxide to the tantalum fluoride aqueous solution to produce a tantalum compound aqueous solution, the hydrogen peroxide solution is added to the tantalum fluoride aqueous solution and mixed to obtain a tantalum compound aqueous solution. It is presumed that at least a portion of the obtained tantalum compound aqueous solution forms a polyacid structure or a peroxo complex structure.
[0141] Here, the hydrogen peroxide concentration of the hydrogen peroxide solution added to the tantalum fluoride aqueous solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably added so that the molar ratio H2O2 / Ta of hydrogen peroxide to tantalum is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing.
[0142] In the reverse neutralization step of adding the obtained tantalum compound aqueous solution to an alkaline aqueous solution to produce a tantalic acid-containing precipitate, the tantalum compound aqueous solution is added to an alkaline aqueous solution, for example, ammonia water, i.e., a reverse neutralization method is used to obtain a tantalum-containing precipitate slurry. Then, fluoride ions are removed from the obtained tantalum-containing precipitate slurry to obtain a tantalum-containing precipitate from which fluoride ions have been removed.
[0143] The ammonia concentration of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, tantalum is less likely to remain undissolved, and tantalum or tantalic acid can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.
[0144] From this viewpoint, the ammonia concentration of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0145] In the reverse neutralization step, the amount of tantalum fluoride aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / Ta is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. In addition, the amount of tantalum fluoride aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more, from the viewpoint of generating amines or tantalic acid compounds that dissolve in dilute ammonia water. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.
[0146] In the reverse neutralization step, the time for adding the tantalum fluoride aqueous solution to the ammonia water is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to add the tantalum fluoride aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the tantalum fluoride aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, in the reverse neutralization step, since the acidic tantalum fluoride aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The tantalum fluoride aqueous solution and the ammonia water can be used at room temperature.
[0147] In the reverse neutralization step, fluoride ions are removed from the tantalum-containing precipitate slurry obtained by the reverse neutralization method, thereby obtaining a tantalum-containing precipitate from which fluoride ions have been removed. Since fluorine compounds such as ammonium fluoride are present as impurities in the tantalum-containing precipitate slurry obtained by the reverse neutralization method, it is preferable to remove these.
[0148] Any method can be used to remove the fluorine compounds, and examples of such methods include filtration using a membrane such as reverse osmosis filtration, ultrafiltration, and microfiltration using aqueous ammonia or pure water, centrifugation, and other known methods. When removing fluoride ions from the tantalum-containing precipitate slurry, there is no particular need to adjust the temperature, and the removal can be carried out at room temperature.
[0149] Specifically, the tantalum-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby obtaining a tantalum-containing precipitate from which the fluoride ions have been removed. Note that by repeating the washing, the hydrogen peroxide added in the reaction step is also removed.
[0150] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water having a concentration of 1% by mass or more and 35% by mass or less is preferable. In the case of such ammonia water, ammonia and ammonium ions are suitable for fluorine, and unnecessary increases in costs can be avoided.
[0151] The tantalum-containing precipitate from which the fluoride ions have been removed through the above-mentioned reaction process and reverse neutralization process is diluted with pure water or the like to obtain a tantalum-containing precipitate slurry from which the fluoride ions have been removed. The tantalum concentration of the tantalum-containing precipitate slurry is measured by taking a portion of the tantalum-containing precipitate slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce Ta2O5. The weight of the Ta2O5 thus produced can be measured, and the tantalum concentration of the tantalum-containing precipitate slurry can be calculated from the weight.
[0152] The tantalum-containing precipitate slurry from which the fluoride ions have been removed, an organic nitrogen compound, and pure water are mixed together and kept at 5°C to 90°C for 0.1 to 48 hours with stirring, thereby obtaining a tantalic acid-containing liquid.
[0153] As described above, the organic nitrogen compound to be mixed with the tantalum-containing precipitation slurry is preferably an aliphatic amine, an aromatic amine, an amino alcohol, an amino acid, a polyamine, a quaternary ammonium, a guanidine compound, or an azole compound, and more preferably an aliphatic amine and / or a quaternary ammonium compound.
[0154] From the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the tantalum-containing precipitation slurry is 40 mass% or less, more preferably 20 mass% or less. From the same viewpoint, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the tantalum-containing precipitation slurry is 0.1 mass% or more, more preferably 1 mass% or more, and may be 5 mass% or more, or may be 10 mass% or more. The aliphatic amine is more preferably methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, or isopropylamine.
[0155] From the viewpoint of solubility, the quaternary ammonium compound is preferably mixed so that the concentration of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 40% by mass or less, and more preferably 20% by mass or less. From the same viewpoint, the quaternary ammonium compound is preferably mixed so that the concentration of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. The quaternary ammonium compound is more preferably tetramethylammonium hydroxide (TMAH) or tetraethylammonium hydroxide (TEAH).
[0156] As another example of the method for producing a metal compound-containing material of the present invention, a method for producing a tungstic acid-containing liquid will be described below.
[0157] The method for producing a tungsten acid-containing liquid includes a step of adding an acidic tungsten aqueous solution containing 1 to 100 g / L of tungsten calculated as WO3 to a 10 to 30 mass % ammonia aqueous solution to generate a tungsten-containing precipitate, and a step of adding an organic nitrogen compound to the tungsten-containing precipitate slurry obtained by forming the tungsten-containing precipitate into a slurry form to generate a tungsten acid-containing liquid.
[0158] First, in the step of adding an acidic tungsten aqueous solution containing 1-100g / L of tungsten in terms of WO3 to a 10-30 mass% ammonia aqueous solution to generate a tungsten-containing precipitate, the acidic tungsten aqueous solution refers to a tungsten sulfate aqueous solution obtained by solvent extraction of a solution in which tungsten is dissolved in an acidic aqueous solution containing sulfuric acid. Note that, unless otherwise specified, tungsten referred to in this specification includes tungsten oxide.
[0159] Here, it is preferable to adjust the tungsten sulfate aqueous solution to contain 1 to 100 g / L of tungsten in terms of WO3 by adding water (e.g., pure water). In this case, it is preferable that the tungsten concentration is 1 g / L or more in terms of WO3, since it becomes a tungsten acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the tungsten concentration is 100 g / L or less in terms of WO3, since it becomes a tungsten acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tungsten acid compound hydrate that is easily soluble in water, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the tungsten sulfate aqueous solution is preferably 2 or less, and more preferably 1 or less, from the viewpoint of completely dissolving tungsten or tungsten oxide.
[0160] When the tungsten sulfate aqueous solution is added to the ammonia aqueous solution, in the so-called reverse neutralization method, it is preferable to add the tungsten sulfate aqueous solution to a 10 mass % to 30 mass % ammonia aqueous solution, that is, to obtain a slurry of a tungsten acid compound hydrate, that is, a slurry of a tungsten-containing precipitate, by the reverse neutralization method.
[0161] The ammonia concentration of the aqueous ammonia solution used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, tungsten is less likely to remain undissolved, and tungsten or tungsten oxide can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous ammonia solution.
[0162] From this viewpoint, the ammonia concentration of the aqueous ammonia solution is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0163] In the reverse neutralization, the amount of tungsten sulfate aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / WO3 is 0.1 or more and 300 or less, more preferably 5 or more and 200 or less. In addition, the tungsten sulfate aqueous solution added to the ammonia water is preferably such that the molar ratio of NH3 / SO4 2- The molar ratio of NH3 / SO4 is preferably 3.0 or more, more preferably 10.0 or more, and even more preferably 20.0 or more. On the other hand, from the viewpoint of cost reduction, the NH3 / SO4 2- The molar ratio of is preferably 200 or less, more preferably 150 or less, and even more preferably 100 or less.
[0164] In the reverse neutralization, the time for adding the tungsten sulfate aqueous solution to the ammonia water is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds. That is, it is preferable to add the tungsten sulfate aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the tungsten sulfate aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, in the reverse neutralization, since the acidic tungsten sulfate aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The tungsten sulfate aqueous solution and the ammonia water can be used at room temperature.
[0165] The sulfur content is then removed from the slurry of the tungsten-containing precipitate obtained by the reverse neutralization method to produce a tungsten-containing precipitate from which the sulfur content has been removed. Since the slurry of the tungsten-containing precipitate obtained by the reverse neutralization method contains, as impurities, sulfate ions that remain without reacting with tungsten or tungsten oxide and sulfur content in the form of hydrogen sulfate ions, it is preferable to remove these.
[0166] Any method for removing sulfur may be used, and for example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, centrifugation, or other known methods may be used. Note that, when removing sulfur from the slurry of the tungsten-containing precipitate, temperature control is not particularly required, and the removal may be performed at room temperature.
[0167] Specifically, the slurry of the tungsten-containing precipitate obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the conductivity of the slurry of the tungsten-containing precipitate becomes 500 μS / cm or less, thereby obtaining a tungsten-containing precipitate from which the sulfur content has been removed. The conductivity was measured by adjusting the liquid temperature of the slurry of the tungsten-containing precipitate to 25° C., immersing the measuring part of a conductivity meter (ASCON2 manufactured by AS ONE CORPORATION) in the supernatant liquid of the slurry of the precipitate, and reading the value after the conductivity value stabilized.
[0168] The cleaning solution used to remove the sulfur content is preferably ammonia water. Specifically, ammonia water of 5.0 mass% or less is preferable, ammonia water of 4.0 mass% or less is more preferable, ammonia water of 3.0 mass% or less is even more preferable, and ammonia water of 2.5 mass% is particularly preferable. When the ammonia water is 5.0 mass% or less, ammonia and ammonium ions are appropriate for the sulfur content, and unnecessary cost increases can be avoided.
[0169] Next, in the step of adding an organic nitrogen compound to the tungsten-containing precipitate slurry obtained by making the tungsten-containing precipitate into a slurry, the tungsten-containing precipitate slurry is obtained by diluting the tungsten-containing precipitate from which sulfur has been removed with pure water or the like to make a slurry. The tungsten concentration of the tungsten-containing precipitate slurry from which sulfur has been removed is measured by taking a part of the slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce WO3. The weight of the WO3 thus produced can be measured, and the tungsten concentration of the slurry can be calculated from the weight.
[0170] Then, by mixing an organic nitrogen compound with the tungsten-containing precipitate slurry from which the sulfur content has been removed, a tungstic acid-containing liquid is obtained.
[0171] Specifically, the obtained tungsten-containing precipitate slurry is added to an organic nitrogen compound and mixed with pure water so that the tungsten concentration in the final mixture is 0.1 to 40 mass% in terms of WO3, and the mixture is stirred while maintaining the liquid temperature at room temperature (25°C) for 1 hour, thereby obtaining a colorless and transparent tungstic acid-containing liquid.
[0172] The organic nitrogen compound mixed with the tungsten-containing precipitation slurry is preferably an aliphatic amine and / or a quaternary ammonium.
[0173] Here, from the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the tungsten-containing precipitation slurry is 40 mass% or less. From the same viewpoint, the aliphatic amine is preferably mixed so that the aliphatic amine concentration in the tungsten-containing precipitation slurry is 0.1 mass% or more, more preferably 20 mass% or more. The aliphatic amine is more preferably methylamine or dimethylamine.
[0174] On the other hand, from the viewpoint of solubility, the quaternary ammonium is preferably mixed so that the quaternary ammonium concentration in the tungsten-containing precipitation slurry is 40 mass% or less. From the same viewpoint, the quaternary ammonium is preferably mixed so that the quaternary ammonium concentration in the tungsten-containing precipitation slurry is 0.1 mass% or more, and more preferably 20 mass% or more. The quaternary ammonium is more preferably tetramethylammonium hydroxide (TMAH).
[0175] Furthermore, the organic nitrogen compound to be mixed with the tungsten-containing precipitation slurry may be a mixture of two or more of aliphatic amines or quaternary ammonium, rather than one of them. For example, a mixture of two or more organic nitrogen compounds such as methylamine and tetramethylammonium hydroxide (TMAH), dimethylamine and tetramethylammonium hydroxide (TMAH), or methylamine and dimethylamine, or a mixture of three or more organic nitrogen compounds such as methylamine, dimethylamine, and tetramethylammonium hydroxide (TMAH) may be used, and may be appropriately changed according to the application.
[0176] As another example of the method for producing a metal compound-containing material of the present invention, a method for producing a zirconium acid-containing liquid will be described below.
[0177] The method for producing a zirconium acid-containing liquid includes the steps of adding hydrogen peroxide to an acidic zirconium aqueous solution containing 1 to 100 g / L of zirconium in terms of ZrO2, and adding the acidic zirconium aqueous solution to which the hydrogen peroxide has been added to a 10 to 30 mass % ammonia aqueous solution to produce a zirconium-containing precipitate, and adding an organic nitrogen compound to a zirconium-containing precipitate slurry obtained by turning the zirconium-containing precipitate into a slurry form, thereby producing a zirconium acid-containing liquid.
[0178] First, hydrogen peroxide is added to an acidic zirconium aqueous solution containing 1 to 100 g / L of zirconium in terms of ZrO2, and the resulting acidic zirconium aqueous solution to which hydrogen peroxide has been added is added to a 10 to 30 mass% ammonia aqueous solution to generate a zirconium-containing precipitate. The acidic zirconium aqueous solution refers to an aqueous zirconium sulfate solution obtained by solvent extraction of a solution in which zirconium is dissolved in an acidic aqueous solution containing sulfuric acid, an aqueous zirconium oxychloride (octahydrate) solution, etc. In addition, zirconium referred to in this specification includes zirconium oxide unless otherwise specified.
[0179] Here, it is preferable to adjust the zirconium sulfate aqueous solution to contain 1 to 100 g / L of zirconium in terms of ZrO2 by adding water (e.g., pure water). In this case, it is preferable that the zirconium concentration is 1 g / L or more in terms of ZrO2, since it is a zirconium oxide hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the zirconium concentration is 100 g / L or less in terms of ZrO2, since it is a zirconium oxide hydrate that is easily soluble in water, and in order to synthesize a zirconium oxide hydrate that is easily soluble in water more reliably, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the zirconium sulfate aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving zirconium or zirconium oxide.
[0180] Next, by adding hydrogen peroxide to the aqueous zirconium sulfate solution, anion species containing zirconium are complexed to form a peroxo complex with excellent dissolution stability. Here, the amount of hydrogen peroxide added to the aqueous zirconium sulfate solution is preferably such that the molar ratio of H2O2 / ZrO2 is 1.0 or more, more preferably 2.5 or more, in terms of excellent solubility. On the other hand, it is preferable that the molar ratio of H2O2 / ZrO2 is 5.0 or less in terms of excellent safety.
[0181] When the thus obtained aqueous zirconium sulfate solution to which hydrogen peroxide has been added is added to an aqueous ammonia solution, in the so-called reverse neutralization method, it is preferable to add the aqueous zirconium sulfate solution to which hydrogen peroxide has been added to an aqueous ammonia solution of 10 mass % to 30 mass % to obtain a slurry of a zirconium oxide compound hydrate, that is, a slurry of a zirconium-containing precipitate.
[0182] The ammonia concentration of the aqueous ammonia solution used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, zirconium is less likely to remain undissolved, and zirconium or zirconium oxide can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous ammonia solution.
[0183] From this viewpoint, the ammonia concentration of the aqueous ammonia solution is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0184] In the reverse neutralization, the amount of the zirconium sulfate aqueous solution to which hydrogen peroxide has been added to be added to the ammonia water is preferably such that the molar ratio of NH3 / ZrO2 is 70 or more and 300 or less, more preferably 100 or more and 300 or less, and even more preferably 140 or more and 300 or less, from the viewpoint of excellent solubility. In addition, the zirconium sulfate aqueous solution to which hydrogen peroxide has been added to be added to the ammonia water has a molar ratio of NH3 / SO4 2- The molar ratio of NH3 / SO4 is preferably 3.0 or more, more preferably 10.0 or more, and even more preferably 20.0 or more. On the other hand, from the viewpoint of cost reduction, the NH3 / SO4 2- The molar ratio of is preferably 200 or less, more preferably 150 or less, and even more preferably 100 or less.
[0185] In the reverse neutralization, the time for adding the zirconium sulfate aqueous solution to which hydrogen peroxide has been added to the ammonia water is preferably within 1 minute, more preferably within 30 seconds, and even more preferably within 10 seconds. That is, it is preferable to add the zirconium sulfate aqueous solution to which hydrogen peroxide has been added in as short a time as possible, for example, all at once, to the ammonia water to carry out the neutralization reaction, rather than gradually adding the zirconium sulfate aqueous solution to which hydrogen peroxide has been added over a period of time. In addition, in the reverse neutralization, the zirconium sulfate aqueous solution to which acidic hydrogen peroxide has been added is added to the alkaline ammonia water, so that the neutralization reaction can be carried out while maintaining a high pH. The zirconium sulfate aqueous solution to which hydrogen peroxide has been added and the ammonia water can be used at room temperature.
[0186] Then, the sulfur content is removed from the slurry of the zirconium-containing precipitate obtained by the reverse neutralization method to produce a zirconium-containing precipitate from which the sulfur content has been removed. Since the slurry of the zirconium-containing precipitate obtained by the reverse neutralization method contains, as impurities, sulfate ions that remain without reacting with zirconium or zirconium oxide and sulfur content in the form of hydrogen sulfate ions, it is preferable to remove these. Note that the added hydrogen peroxide is not removed and remains together with the zirconium-containing precipitate.
[0187] Any method for removing sulfur may be used, and for example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, centrifugation, or other known methods may be used. Note that, when removing sulfur from the slurry of the zirconium-containing precipitate, temperature control is not particularly required, and the removal may be performed at room temperature.
[0188] Specifically, the zirconium-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the conductivity of the zirconium-containing precipitate slurry becomes 500 μS / cm or less, thereby obtaining a zirconium-containing precipitate from which sulfur has been removed. The conductivity was measured by adjusting the liquid temperature of the zirconium-containing precipitate slurry to 25° C., immersing the measuring part of a conductivity meter (ASCON2 manufactured by AS ONE CORPORATION) in the supernatant liquid of the precipitate slurry, and reading the conductivity value after it stabilized.
[0189] The cleaning solution used to remove the sulfur content is preferably ammonia water. Specifically, ammonia water of 5.0 mass% or less is preferable, ammonia water of 4.0 mass% or less is more preferable, ammonia water of 3.0 mass% or less is even more preferable, and ammonia water of 2.5 mass% is particularly preferable. When the ammonia water is 5.0 mass% or less, ammonia and ammonium ions are appropriate for the sulfur content, and unnecessary cost increases can be avoided.
[0190] Next, in the step of adding an organic nitrogen compound to the zirconium-containing precipitate slurry obtained by making the zirconium-containing precipitate into a slurry form, the zirconium-containing precipitate slurry is obtained by diluting the zirconium-containing precipitate from which the sulfur content has been removed with pure water or the like to make it into a slurry form as described above. The zirconium concentration of the zirconium-containing precipitate slurry from which the sulfur content has been removed is measured by taking a part of the slurry, drying it at 110°C for 24 hours, and then firing it at 1,000°C for 4 hours to produce ZrO2. The weight of the ZrO2 thus produced can be measured, and the zirconium concentration of the slurry can be calculated from the weight.
[0191] Then, by mixing an organic nitrogen compound with the zirconium-containing precipitate slurry from which the sulfur content has been removed, a zirconium acid-containing liquid is obtained.
[0192] Specifically, the obtained zirconium-containing precipitate slurry is added to an organic nitrogen compound and mixed with pure water so that the zirconium concentration in the final mixture is 0.1 to 10 mass% in terms of ZrO2, and the mixture is stirred while maintaining the liquid temperature at room temperature (25°C) for 1 hour, thereby obtaining a yellow or colorless and transparent zirconium acid-containing liquid.
[0193] The organic nitrogen compound which is mixed with the zirconium-containing precipitation slurry is preferably a quaternary ammonium compound.
[0194] Here, from the viewpoint of solubility, the quaternary ammonium is preferably mixed so that the concentration of the quaternary ammonium in the zirconium-containing precipitation slurry is 40 mass% or less. From the same viewpoint, the quaternary ammonium is preferably mixed so that the concentration of the quaternary ammonium in the zirconium-containing precipitation slurry is 0.1 mass% or more, and more preferably 20 mass% or more.
[0195] Moreover, the quaternary ammonium is more preferably tetramethylammonium hydroxide (TMAH). The amount of tetramethylammonium hydroxide (TMAH) added to the zirconium-containing precipitation slurry is preferably such that the molar ratio of TMAH / ZrO2 is 1.5 or more in terms of excellent solubility and stability, and more preferably such that the molar ratio is 2.0 or more in terms of even better stability. On the other hand, the molar ratio of TMAH / ZrO2 is 5.0 or less in terms of excellent safety. If the molar ratio of TMAH / ZrO2 is less than 1.0, the zirconium-containing precipitation slurry does not dissolve, and if it is 1.0 to 1.4, the zirconium-containing precipitation slurry dissolves but gels.
[0196] Furthermore, the organic nitrogen compound to be mixed with the zirconium-containing precipitation slurry may be a mixture of two or more quaternary ammonium compounds, rather than one type. For example, a mixture of two or more organic nitrogen compounds such as tetramethylammonium hydroxide (TMAH) and methylamine, or tetramethylammonium hydroxide (TMAH) and dimethylamine, or a mixture of three or more organic nitrogen compounds such as tetramethylammonium hydroxide (TMAH), methylamine, and dimethylamine may be used, and may be appropriately changed according to the application.
[0197] Furthermore, among the metal compounds used in the method for producing a metal compound-containing material of the present invention, for example, a niobic acid-containing liquid can be produced by the following production method in addition to the above-mentioned method for producing a niobic acid-containing liquid.
[0198] First, niobium, niobium oxide, or niobium hydroxide is reacted with hydrofluoric acid (HF) such as hydrofluoric acid solution to form niobium fluoride (H2NbF7), which is then dissolved in water to obtain an acidic metal aqueous solution, a niobium fluoride aqueous solution. In the case of niobium chloride, it is possible to omit the step of dissolving in hydrofluoric acid and add water to niobium chloride to produce an acidic niobium aqueous solution.
[0199] Here, it is preferable to adjust the niobium fluoride aqueous solution to contain 1 to 100 g / L of niobium in terms of Nb2O5 by adding water (e.g., pure water). In this case, it is preferable that the niobium concentration is 1 g / L or more in terms of Nb2O5, since it becomes a niobium acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the niobium concentration is 100 g / L or less in terms of Nb2O5, since it becomes a niobium acid compound hydrate that is easily soluble in water, and in order to synthesize a niobium acid compound hydrate that is easily soluble in water more reliably, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the niobium fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving niobium or niobium oxide.
[0200] Next, the niobium fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing niobium hydrate cake. Here, the alkaline aqueous solution used to neutralize the niobium fluoride aqueous solution is preferably 10% by mass to 30% by mass ammonia water.
[0201] The ammonia concentration of the ammonia water used for neutralization is preferably 10% by mass to 30% by mass. When the ammonia concentration is 10% by mass, niobium is less likely to remain undissolved, and niobium or niobic acid can be completely dissolved in water. On the other hand, when the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.
[0202] From this viewpoint, the ammonia concentration of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0203] In the neutralization reaction described above, the amount of addition is preferably such that the molar ratio of NH3 / Nb is 95 or more and 500 or less, more preferably such that the molar ratio of NH3 / Nb is 100 or more and 450 or less, and even more preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably such that the molar ratio of NH3 / HF is 4.0 or more, and even more preferably such that the molar ratio of NH3 / HF is 5.0 or more, from the viewpoint of generating a niobic acid compound that dissolves in amine or dilute ammonia water. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably such that the molar ratio of NH3 / HF is 50 or less, and even more preferably such that the molar ratio of NH3 / HF is 40 or less.
[0204] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to carry out the neutralization reaction in as short a time as possible, for example, by adding all at once, rather than gradually adding over a long period of time. The niobium fluoride aqueous solution and ammonia water can be used at room temperature.
[0205] The fluorine-containing niobium hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing niobium hydrate cake and obtaining a niobium-containing precipitate. Since the fluorine-containing niobium hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, it is preferable to remove these.
[0206] The niobium concentration of the obtained niobium-containing precipitate is measured by taking a portion of the niobium-containing precipitate, drying it at 110°C for 24 hours, and then calcining it at 1000°C for 4 hours to produce Nb2O5. The weight of the Nb2O5 thus produced is measured, and the niobium concentration of the niobium-containing precipitate can be calculated from the weight.
[0207] The cleaning liquid used to remove fluoride ions is preferably dilute ammonia water. Specifically, dilute ammonia water of 1 mass% or more and 35 mass% or less is preferable. In such dilute ammonia water, ammonia and ammonium ions are suitable for fluorine, and unnecessary cost increase can be avoided.
[0208] The method for removing the fluorine compounds is arbitrary, and for example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, centrifugation, or other known methods can be used. In addition, when removing fluoride ions from the fluorine-containing niobium hydrate cake, there is no particular need to adjust the temperature, and the removal can be carried out at room temperature.
[0209] Then, an amine compound and pure water are added to the obtained niobium-containing precipitate and stirred for 10 minutes to obtain a niobium-containing mixed liquid. After that, 35 mass % hydrogen peroxide is added to the niobium-containing mixed liquid and stirred for 30 minutes to obtain a niobic acid compound-containing liquid.
[0210] From the viewpoint of solubility, the amine compound is preferably mixed so that the amine compound concentration in the niobium-containing mixed solution is 30% by mass or less, more preferably 20% by mass or less. From the same viewpoint, the amine compound is preferably mixed so that the amine compound concentration in the niobium-containing mixed solution is 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. Furthermore, the amine compound is preferably a tertiary amine compound, more preferably one or more selected from methylamine, ethylamine, triethylamine, ethylamine, diethylamine, triethylamine, and tri-n-propylamine, and even more preferably one or more selected from trimethylamine, triethylamine, and tri-n-propylamine.
[0211] The hydrogen peroxide concentration of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably added so that the molar ratio H2O2 / Nb of hydrogen peroxide to niobium is 0.6 to 1.5, and more preferably 0.7 to 1.2 because hydrogen peroxide may decompose during mixing.
[0212] In addition, the above-mentioned method for producing a niobic acid compound-containing liquid preferably includes a step of removing hydrogen peroxide from the obtained niobic acid compound-containing liquid, because if hydrogen peroxide is contained in the niobic acid compound-containing liquid, the inside of a sealed container will be filled with gas generated by decomposition of hydrogen peroxide, which may cause the container to expand or, in the worst case, burst.
[0213] The hydrogen peroxide can be removed by any method, for example, stirring under open or reduced pressure conditions, or drying under reduced pressure.
[0214] In addition to the above-mentioned method for producing a tantalic acid-containing liquid, the tantalic acid-containing liquid can also be produced by the following production method. Note that the description of the same part as the above-mentioned method for producing a niobic acid-containing liquid will be omitted.
[0215] First, tantalum, tantalum oxide, tantalum hydroxide, or tantalum alkoxide is reacted with hydrofluoric acid (HF) such as hydrofluoric acid solution to form tantalum fluoride (H2TaF7), which is then dissolved in water to obtain an acidic metal aqueous solution, a tantalum fluoride aqueous solution. In the case of tantalum chloride, it is possible to omit the step of dissolving in hydrofluoric acid and add water to tantalum chloride to produce an acidic tantalum aqueous solution.
[0216] Here, it is preferable to adjust the tantalum fluoride aqueous solution to contain tantalum at 1 to 100 g / L in terms of Ta2O5 by adding water (e.g., pure water). In this case, it is preferable that the tantalum concentration is 1 g / L or more in terms of Ta2O5, since the tantalum acid compound hydrate is easily soluble in water, and in consideration of productivity, it is more preferable that the tantalum concentration is 10 g / L or more, and even more preferable that the tantalum concentration is 20 g / L or more. On the other hand, it is preferable that the tantalum concentration is 100 g / L or less in terms of Ta2O5, since the tantalum acid compound hydrate is easily soluble in water, and in order to more reliably synthesize the tantalum acid compound hydrate that is easily soluble in water, it is more preferable that the tantalum concentration is 90 g / L or less, even more preferable that the tantalum concentration is 80 g / L or less, and particularly preferable that the tantalum concentration is 70 g / L or less. In addition, the pH of the tantalum fluoride aqueous solution is preferably 2 or less, and more preferably 1 or less, from the viewpoint of completely dissolving tantalum or tantalum oxide.
[0217] Next, the tantalum fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing tantalum hydrate cake. Here, the alkaline aqueous solution used to neutralize the tantalum fluoride aqueous solution is preferably 10% by mass to 30% by mass of ammonia water.
[0218] In the neutralization reaction described above, the amount of addition is preferably such that the molar ratio of NH3 / Ta is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. From the viewpoint of generating a tantalic acid compound that is soluble in amine or dilute ammonia water, the amount of addition is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.
[0219] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes.
[0220] The fluorine-containing tantalum hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing tantalum hydrate cake and obtaining a tantalum-containing precipitate. The fluorine-containing tantalum hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, so it is preferable to remove these. It is preferable that the washing liquid used to remove the fluoride ions is dilute ammonia water.
[0221] The tantalum concentration of the obtained tantalum-containing precipitate is determined by taking a portion of the tantalum-containing precipitate, drying it at 110°C for 24 hours, and then firing it at 1000°C for 4 hours to produce Ta2O5. The weight of the Ta2O5 produced in this manner is measured, and the tantalum concentration of the tantalum-containing precipitate can be calculated from that weight.
[0222] Then, an amine compound and pure water are added to the obtained tantalum-containing precipitate and stirred for 10 minutes to obtain a tantalum-containing mixed liquid. After that, 35 mass % hydrogen peroxide is added to the tantalum-containing mixed liquid and stirred for 30 minutes to obtain a tantalic acid compound-containing liquid.
[0223] From the viewpoint of solubility, the amine compound is preferably mixed so that the amine compound concentration in the tantalum-containing mixed solution is 0.1 mass % or more and 30 mass % or less. The amine compound is preferably a tertiary amine compound, more preferably one or more selected from methylamine, ethylamine, triethylamine, ethylamine, diethylamine, triethylamine, and tri-n-propylamine, and even more preferably one or more selected from trimethylamine, triethylamine, and tri-n-propylamine.
[0224] The hydrogen peroxide concentration of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably added so that the molar ratio H2O2 / Ta of hydrogen peroxide to tantalum is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing.
[0225] As in the above-mentioned method for producing a niobate compound-containing liquid, it is preferable to have a step of removing hydrogen peroxide from the obtained tantalate compound-containing liquid.
[0226] Furthermore, metal compound-containing liquids containing two or more of the following liquids can be produced by a similar production method: titanic acid-containing liquid, niobic acid-containing liquid, molybdic acid-containing liquid, hafnic acid-containing liquid, tantalic acid-containing liquid, tungstic acid-containing liquid, and zirconic acid-containing liquid; and metal acid salt-containing liquids in which these metal compound-containing liquids are ionically bonded to alkali metal ions (e.g., lithium ions).
[0227] As another example of the method for producing a metal compound-containing material of the present invention, a method for producing a metal compound-containing material using a complex polymerization method will be described below.
[0228] A method for producing a metal compound-containing material using a complex polymerization method includes a complexing step of mixing a metal hydroxide with an alkaline solution to produce a first mixed liquid, adding hydrogen peroxide to the first mixed liquid to produce a second mixed liquid, and further adding an organic acid to the second mixed liquid to produce the metal compound-containing material.
[0229] In the complexing step in the method for producing a metal compound-containing material using a complex polymerization method, a metal hydroxide described below is first mixed with an alkaline solution to produce a first mixed liquid.
[0230] The metal hydroxide is preferably a hydroxide of tantalum, niobium, titanium, tungsten, molybdenum, zirconium, etc. In particular, the metal hydroxide is preferably tantalum hydroxide or niobium hydroxide.
[0231] For example, it is preferable to adjust tantalum hydroxide to contain 1 to 100 g / L of tantalum in terms of Ta2O5 by adding water (e.g., pure water). In this case, it is preferable that the tantalum concentration is 1 g / L or more in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the tantalum concentration is 100 g / L or less in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tantalic acid compound hydrate that is easily soluble in water, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. Similarly, it is preferable to adjust niobium hydroxide to contain 1 to 100 g / L of niobium in terms of Nb2O5.
[0232] The alkaline solution is preferably an alkaline solution in which one or more compounds selected from ammonia water, sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, and organic nitrogen compounds are dissolved. Examples of the organic nitrogen compounds include amine compounds, quaternary ammonium compounds, guanidine compounds, and azole compounds, and the like are preferably amine compounds or quaternary ammonium compounds, and more preferably methylamine, dimethylamine, tetramethylammonium hydroxide (TMAH), and tetraethylammonium hydroxide (TEAH). Examples of the solvent include water, organic solvents, and mixed solvents thereof. The alkaline solution is particularly preferably an alkaline solution, and especially preferably ammonia water.
[0233] The ammonia concentration of the ammonia water is preferably 10% by mass to 30% by mass. Here, when the mixed metal hydroxide is tantalum hydroxide or niobium hydroxide, if the ammonia concentration is 10% by mass or more, tantalum or niobium is less likely to remain undissolved, and tantalum or niobium can be completely dissolved in water. On the other hand, if the ammonia concentration is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.
[0234] From this viewpoint, the ammonia concentration of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia concentration is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.
[0235] Regarding the amount of ammonia water added, when the metal hydroxide to be mixed is tantalum hydroxide, the molar ratio of NH3 / Ta is preferably 0.1 or more and 100 or less, and more preferably 1 or more and 50 or less. From the viewpoint of reactivity and dispersibility (solubility) with tantalum hydroxide, the molar ratio of NH3 / Ta is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more. On the other hand, from the viewpoint of cost reduction, the molar ratio of NH3 / Ta is preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less. Furthermore, when the metal hydroxide to be mixed is niobium hydroxide, the molar ratio of NH3 / Nb is preferably 0.1 or more and 100 or less, and more preferably 1 or more and 50 or less. From the viewpoint of reactivity and dispersibility (solubility) with niobium hydroxide, the molar ratio of NH3 / Nb is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more. On the other hand, from the viewpoint of cost reduction, the molar ratio of NH3 / Nb is preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less.
[0236] Next, in the complexing step in the method for producing a metal compound-containing material using a complex polymerization method, hydrogen peroxide, which will be described below, is added to the first mixed liquid thus produced to produce a second mixed liquid.
[0237] The concentration of hydrogen peroxide is preferably 0.5% by mass to 35% by mass. When the metal hydroxide to be mixed is tantalum hydroxide, hydrogen peroxide is preferably added so that the molar ratio H2O2 / Ta between hydrogen peroxide and tantalum is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing. Furthermore, when the metal hydroxide to be mixed is niobium hydroxide, hydrogen peroxide is preferably added so that the molar ratio H2O2 / Nb between hydrogen peroxide and niobium is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing.
[0238] Here, when hydrogen peroxide is added under alkaline conditions, the complexation reaction is more likely to proceed, so it is advisable to mix a metal hydroxide with an alkaline solution before adding hydrogen peroxide to produce a first mixed liquid, which is an alkaline solution.
[0239] In the complexing step in the method for producing a metal compound-containing material using the complex polymerization method, an organic acid described below is added to the second mixed liquid to produce a metal compound-containing material.
[0240] Examples of organic acids include carboxylic acids, polyfunctional carboxylic acids, hydroxycarboxylic acids, and amino acids. Examples of carboxylic acids include butyric acid, formic acid, acetic acid, lauric acid, oleic acid, linoleic acid, and benzoic acid. Examples of polyfunctional carboxylic acids include oxalic acid, succinic acid, malonic acid, maleic acid, glutaric acid, and citric acid. Examples of hydroxycarboxylic acids include lactic acid, gluconic acid, tartaric acid, and malic acid. Examples of amino acids include alanine, arginine, aspartic acid, and ethylenediaminetetraacetic acid. In particular, organic acids that do not contain nitrogen atoms are preferred, such as carboxylic acids, polyfunctional carboxylic acids, and hydroxycarboxylic acids, more preferably polyfunctional carboxylic acids, and most preferably citric acid, which is an organic acid that does not contain nitrogen atoms and is a polyfunctional carboxylic acid. The organic acids also include various isomers (structural isomers, optical isomers, and the like) of the above-mentioned compounds. Furthermore, the organic acid may be one or more organic acids of the above-mentioned compounds.
[0241] The organic acid, for example, citric acid, is preferably added at a concentration of 1% by mass to 100% by mass. When the metal hydroxide to be mixed is tantalum hydroxide, it is preferable to add citric acid so that the molar ratio of citric acid to tantalum, C6H8O7 / Ta, is 0.1 or more and 100 or less, and from the viewpoints of stability and cost reduction of the metal compound-containing material, it is more preferable that the molar ratio is 0.5 or more and 50 or less. Furthermore, when the metal hydroxide to be mixed is niobium hydroxide, it is preferable to add citric acid so that the molar ratio of citric acid to niobium, C6H8O7 / Nb, is 0.1 or more and 100 or less, and from the viewpoints of stability and cost reduction of the metal compound-containing material, it is more preferable that the molar ratio is 0.5 or more and 50 or less.
[0242] The complexing step in the above-mentioned method for producing a metal compound-containing material using the complex polymerization method does not require heating and can be carried out at room temperature (25° C.).
[0243] It is presumed that at least a portion of the metal compound-containing material thus produced forms a peroxo complex containing the metal element derived from the metal hydroxide.
[0244] The metal compound-containing material produced using the complex polymerization method may have a drying step of drying the metal compound-containing material. By drying the metal compound-containing material produced in the complexing step by a drying method described below, it is possible to remove excess hydrogen peroxide and ammonia contained in the metal compound-containing material.
[0245] By removing excess hydrogen peroxide from the metal compound-containing material, it is possible to suppress changes in the solution caused by the evaporation of hydrogen peroxide, and it is also easier to use from a safety and legal standpoint. Specifically, if the hydrogen peroxide content in the metal compound-containing material is 6% by mass or less, it is exempt from the Deleterious Substances Control Law, making it easier to use in terms of safety and storage methods. In addition, by removing excess ammonia contained in the metal compound-containing material, it is easier to use in terms of safety and work.
[0246] As an example of the drying step in the method for producing a metal compound-containing material using the complex polymerization method, the heating temperature in the drying step is preferably less than 100°C. If the heating temperature in the drying step is 25°C or higher but lower than 100°C, the excess hydrogen peroxide and ammonia contained in the metal compound-containing material will volatilize, resulting in a white peroxo complex powder. The heating temperature is more preferably 90°C or lower. The heating time is preferably 1 hour or higher but 100 hours or lower, and more preferably 5 hours or higher but 20 hours or lower.
[0247] In another example of the drying step in the method for producing a metal compound-containing material using the complex polymerization method, the heating temperature in the drying step is preferably 100° C. or higher. When the heating temperature in the drying step is 100° C. or higher and 200° C. or lower, the excess hydrogen peroxide and ammonia contained in the metal compound-containing material are volatilized, and a greenish-white peroxo complex powder is obtained. The heating temperature is more preferably 110° C. or higher. The heating time is preferably 1 hour or higher and 100 hours or lower, and more preferably 5 hours or higher and 20 hours or lower.
[0248] Furthermore, as another example of the drying step in the method for producing a metal compound-containing material using the complex polymerization method, a white peroxo complex powder is obtained by a drying method using vacuum drying without heating. The heating time is preferably 1 hour or more and 100 hours or less, and more preferably 5 hours or more and 20 hours or less. In the case of vacuum drying, the excess hydrogen peroxide and ammonia components contained in the metal compound-containing material are not removed and remain.
[0249] The method for producing a metal compound-containing material using a complex polymerization method may further include a crushing step of crushing the metal compound-containing material dried in the drying step. The peroxo complex powder, which is the dried metal compound-containing material obtained by each of the drying steps described above, is pulverized using a ball mill, a jet mill, a cutter mill, etc. By pulverizing the peroxo complex powder, the peroxo complex powder is preferably dissolved in pure water more easily.
[0250] The metal compound-containing material of the present invention may also be a metal compound-containing material containing a resin, which is produced by weighing out the metal compound-containing material obtained by the above-mentioned method for producing a metal compound-containing material, a resin, and a solvent in predetermined proportions, mixing them, and stirring for 30 minutes.
[0251] Here, the above-mentioned resin is preferably an anionic water-soluble resin and / or a nonionic water-soluble resin.Furthermore, the resin may contain one or more water-soluble homopolymers selected from the group consisting of acrylic polymers, urethane polymers, styrene polymers, olefin polymers, amide polymers, siloxane polymers, epoxy polymers, vinyl chloride polymers, and vinyl acetate polymers, and / or water-soluble copolymers consisting of two or more of these polymers.In particular, the resin is preferably one or more water-soluble homopolymers of acrylic polymers, styrene polymers, and olefin polymers, and / or water-soluble copolymers consisting of two or more of these polymers.
[0252] Moreover, the above-mentioned solvent may be water.
[0253] The metal compound-containing material of the present invention thus obtained is applied onto a carbon substrate, and the applied carbon substrate is heated, whereby a metal-carbon composite coating can be formed on the carbon substrate.
[0254] Here, the metal-carbon composite coating formed on the carbon substrate may be, for example, a metal-carbon composite coating on at least one side (e.g., the surface) of the carbon substrate, or a metal-carbon composite coating on the entire peripheral surface of the carbon substrate, and further includes a metal-carbon composite coating on only a portion of one side of the carbon substrate.
[0255] First, the metal compound-containing material of the present invention is applied onto a carbon substrate (hereinafter, also referred to as the application step).
[0256] Methods for applying the metal compound-containing material onto the carbon substrate include spraying, inkjet, dispenser, nozzle coating, slit coating, die coating, roll coating, spin coating, blade coating, knife coating, wire bar coating, screen printing, brush coating, and the like.
[0257] Next, the carbon substrate coated with the metal compound-containing material is heated to form a metal-carbon composite coating on the carbon substrate (hereinafter, also referred to as the heating step).
[0258] By heating the carbon substrate to which the metal compound-containing substance has been applied, the metal compound-containing substance reacts with the carbon contained in the carbon substrate, i.e., a carbonization reaction occurs, and a metal-carbon composite coating is formed on the carbon substrate.
[0259] Specifically, the carbon substrate coated with the metal compound-containing material is placed in a static furnace and heated under an inert atmosphere, for example, under an argon atmosphere or a nitrogen atmosphere, whereby the metal element in the metal compound-containing material reacts (carbonization reaction) with the carbon present on the coating surface of the carbon substrate coated with the metal compound-containing material to form a metal carbide, and a metal-carbon composite coating can be formed on the carbon substrate. The heating step may be performed under reduced pressure or in a vacuum. Here, it is preferable that the heating temperature in the heating step is 1000°C or higher and 3500°C or lower, and the heating time is 0.5 hours or higher and 2 hours or lower.
[0260] Furthermore, when the metal compound-containing material is a peroxo complex metal compound, by heating the carbon substrate to which the peroxo complex metal compound is applied, the metal element contained in the peroxo complex metal compound reacts with carbon to form a metal carbide, and a metal-carbon composite coating can be formed on the carbon substrate.
[0261] The heating temperature in the heating step is preferably 1000° C. or higher and 3500° C. or lower in order to ensure a reaction between the carbon of the carbon base material and the metal compound. The heating temperature in the heating step is more preferably 1400° C. or higher and 2000° C. or lower, even more preferably 1500° C. or higher and 1900° C. or lower, and particularly preferably 1550° C. or higher and 1800° C. or lower.
[0262] The heating time in the heating step is preferably 0.5 hours or more and 2 hours or less in terms of sufficient synthesis of the charcoal, more preferably 1 hour or more and 1.5 hours or less, and even more preferably 1.2 hours or more and 1.4 hours or less.
[0263] A drying step may be included between the coating step and the heating step.
[0264] It is preferable to place the carbon substrate coated with the metal compound-containing material in a static furnace and dry it at a drying temperature of 100° C. for 1 hour, since this makes it possible to remove excess impurities such as moisture.
[0265] The drying temperature in the drying step is more preferably 110°C or higher and 400°C or lower, further preferably 120°C or higher and 300°C or lower, and particularly preferably 130°C or higher and 200°C or lower.
[0266] The drying time in the drying step is preferably from 0.2 hours to 3 hours, more preferably from 0.3 hours to 2 hours, and even more preferably from 0.4 hours to 1 hour.
[0267] Furthermore, the method may include a step of cooling the metal-carbon composite coating formed by the heating step. The metal-carbon composite coating formed by the heating step may be allowed to cool to room temperature.
[0268] Specifically, the carbon substrate on which the metal-carbon composite coating has been formed is removed from the static furnace and allowed to cool to room temperature.
[0269] The method for producing a metal-carbon composite coating on a carbon substrate using the metal compound-containing material of the present invention may be the following production method.
[0270] A metal-carbon composite coating is formed on the carbon substrate by immersing the carbon substrate in a material containing a metal compound and heating the immersed carbon substrate.
[0271] First, the carbon substrate is immersed in a material containing a metal compound (hereinafter, also referred to as the immersion step).
[0272] Specifically, the carbon substrate is immersed in a container filled with the metal compound-containing material, so that the carbon substrate is impregnated with the metal compound-containing material. The immersion time in the immersion step is preferably 0.1 to 1 hour, more preferably 0.2 to 0.9 hours. The immersion step may be performed at room temperature, or may be heated and then cooled to room temperature.
[0273] In addition, the immersion step is preferably carried out under reduced pressure or in vacuum, in that the carbon substrate is immersed in the metal compound-containing material, which makes it easier for the carbon substrate to be impregnated with the metal compound-containing material and shortens the immersion time in the immersion step.
[0274] Specifically, a container filled with the metal compound-containing material in which the carbon substrate is immersed is placed in a pressure reducing device and placed under reduced pressure or vacuum, which makes it easier for the metal compound-containing material to be impregnated into the carbon substrate.
[0275] The degree of vacuum in the pressure reducing device is preferably 0.05 MPa or less, more preferably 0.04 MPa or less, even more preferably 0.03 MPa or less, and particularly preferably 0.02 MPa or less. The immersion time in the immersion step under reduced pressure or vacuum is preferably 0.1 hour to 0.5 hours, and more preferably 0.2 hour to 0.4 hours.
[0276] Furthermore, when a metal-carbon composite coating is formed only on one surface of the carbon substrate, for example, on the surface, only the surface of the carbon substrate is immersed in the metal compound-containing material, whereas when a metal-carbon composite coating is formed on the entire peripheral surface of the carbon substrate, the entire peripheral surface of the carbon substrate is immersed in the metal compound-containing material.
[0277] Next, the carbon substrate impregnated with the metal compound-containing material is heated to form a metal-carbon composite coating on the carbon substrate (hereinafter, also referred to as the heating step). By heating the carbon substrate impregnated with the metal compound-containing material, the metal element in the metal compound-containing material reacts (carbonization reaction) with the carbon present in the carbon substrate impregnated with the metal compound-containing material to form a metal carbide, and a metal-carbon composite coating is formed on the carbon substrate.
[0278] Here, when the metal compound-containing material is a metal peroxocitrate compound, by heating the carbon substrate impregnated with the metal peroxocitrate compound, the metal element contained in the metal peroxocitrate compound reacts with carbon to form a metal carbide, and a metal-carbon composite coating can be formed on the carbon substrate.
[0279] The heating step is characterized in that the temperature is 1000° C. or more and 3500° C. or less, and the heating time is 0.5 hours or more and 2 hours or less.
[0280] The heating temperature in the heating step is preferably 1000° C. or higher and 3500° C. or lower in order to ensure a reaction between the carbon of the carbon base material and the metal compound. The heating temperature in the heating step is more preferably 1400° C. or higher and 2000° C. or lower, even more preferably 1500° C. or higher and 1900° C. or lower, and particularly preferably 1550° C. or higher and 1800° C. or lower.
[0281] The heating time in the heating step is preferably 0.5 hours or more and 2 hours or less in terms of sufficient synthesis of the charcoal, more preferably 1 hour or more and 1.5 hours or less, and even more preferably 1.2 hours or more and 1.4 hours or less.
[0282] Furthermore, a drying step may be further included between the above-mentioned immersion step and heating step.
[0283] It is preferable to place the carbon substrate impregnated with the metal compound-containing material in a static furnace and dry it at a drying temperature of 100° C. for 1 hour, since this makes it possible to remove excess impurities such as moisture.
[0284] The drying temperature in the drying step is more preferably 110°C or higher and 400°C or lower, further preferably 120°C or higher and 300°C or lower, and particularly preferably 130°C or higher and 200°C or lower.
[0285] The drying time in the drying step is preferably from 0.2 hours to 3 hours, more preferably from 0.3 hours to 2 hours, and even more preferably from 0.4 hours to 1 hour.
[0286] Furthermore, the method may include a step of cooling the metal-carbon composite coating formed by the heating step. The metal-carbon composite coating formed by the heating step may be allowed to cool to room temperature.
[0287] The metal-carbon composite coating formed on the carbon substrate may be in a state in which a metal element and carbon are present, and preferably the metal element is more than 0 mass% and not more than 80 mass%, and the carbon is more than 0 mass% and not more than 50 mass%. The mass fractions of the metal element and carbon in the metal-carbon composite coating can be measured, for example, by semi-quantitative analysis using energy dispersive X-ray analysis (EDX) of the metal-carbon composite coating portion on a cross-sectional sample of the substrate.
[0288] Furthermore, while the metal elements in the metal-carbon composite coating are present in large amounts on the coating surface, the closer to the carbon substrate the greater the proportion of carbon derived from the carbon substrate. When a substance containing a metal compound is applied, the metal elements are more likely to be present on the surface of the metal-carbon composite coating. On the other hand, when the substance containing a metal compound is impregnated, the proportion of metal elements inside the metal-carbon composite coating is relatively greater than when the substance is applied.
[0289] In addition, the metal-carbon composite coating formed on the carbon substrate can be confirmed to be a carbide from the peaks in the X-ray diffraction pattern obtained by performing X-ray diffraction measurement according to the X-ray diffraction measurement conditions and X-ray diffraction analysis conditions described below.
[0290] =X-ray diffraction measurement conditions= Equipment: MiniFlexII (Rigaku Corporation) Measurement range (2θ): 5~90° Sampling width: 0.02° Scan speed: 2.0° / min ·X-ray: CuKα ray Voltage: 30kV ·Current: 15mA Divergence slit: 1.25° Scattering slit: 1.25° Receiving slit: 0.3 mm
[0291] =X-ray diffraction analysis conditions= Use Rigaku's data analysis software PDXL2. · Smooth the peaks with b-spline to clarify the peak tops.
[0292] Furthermore, if the thickness of the metal-carbon composite coating formed on the carbon substrate is 300 nm or less, it is preferable in that cracks in the film and peeling of the film itself are unlikely to occur. The thickness of the metal-carbon composite coating may be 100 nm or less. If cracks occur in the metal-carbon composite coating, the carbon substrate is oxidized and easily released as carbon dioxide, and carbon in the carbon substrate is likely to decrease. On the other hand, if the thickness of the metal-carbon composite coating is 1 nm or more, it is preferable in that the carbon substrate can be sufficiently protected. The thickness of the metal-carbon composite coating may be 10 nm or more.
[0293] Furthermore, by forming a metal-carbon composite coating on a carbon substrate, it is possible to improve corrosion resistance against the following liquids and gases: hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, hydrofluoric acid, sodium chloride, acetic acid, oxalic acid, ammonia water, sodium hydroxide, potassium hydroxide, water vapor, hydrogen sulfide gas, ammonia gas, hydrogen gas, fluorine gas, chlorine gas, nitrogen oxide gas (NOx), and sulfur oxide gas (SOx).
[0294] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention
[0295] The metal compound-containing material of the present invention can form a protective film on the surface of the substrate without the need for a CVD device. [Brief description of the drawings]
[0296] [Figure 1] 1 is a table showing physical property values of metal compound-containing materials according to Examples 1 to 10 of the present invention, a coated structure according to Comparative Example 1, and carbon substrates according to Reference Example 1 and Comparative Examples 3 and 4. [Diagram 2] 1 is a table showing physical property values of metal compound-containing materials according to Examples 11 to 17 of the present invention and carbon substrates according to Comparative Examples 5 and 6. [Diagram 3] 1 is a table showing physical property values of the metal compound-containing materials according to Examples 18 and 19 of the present invention and the carbon substrate according to Comparative Example 7. [Figure 4] 1 is a table showing physical property values of metal acid compound-containing liquids according to Experimental Examples 1 to 19 of the present invention and Comparative Example 2. [Diagram 5] 1 is a table showing the measurement results of metal acid compound-containing liquids according to Experimental Examples 1 to 19 of the present invention and Comparative Example 2. [Figure 6] 1 is a table listing physical property values and measurement results of metal acid compound-containing liquids according to Experimental Examples 2 to 6, 13, 15, 17 to 19 of the present invention and Comparative Example 2. BEST MODE FOR CARRYING OUT THEINVENTION
[0297] The metal compound-containing material according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.
[0298] Example 1 The metal compound-containing material according to Example 1 was obtained as follows. 200 g of tantalum hydroxide and 92 g of 25 mass% ammonia water were stirred and mixed for 10 minutes to obtain a first mixed liquid. Then, 220 g of 35 mass% hydrogen peroxide water was further added to the first mixed liquid and stirred for 10 minutes to obtain a second mixed liquid. Then, 79 g of citric acid was added to the second mixed liquid and stirred for 10 minutes to obtain a tantalum peroxocitrate solution as the metal compound-containing material according to Example 1. Here, the tantalum concentration of the tantalum peroxocitrate solution, which is the metal compound-containing material according to Example 1, was 18% in terms of Ta2O5 and 14.3% in terms of Ta.
[0299] The metal compound-containing material according to Example 1 was a transparent solution without precipitation immediately after production, and was also a transparent solution without precipitation 7 days after production. The metal compound-containing material according to Example 1 had a Ta2O5 equivalent concentration of 175 g / L after 7 days of production. Furthermore, the average particle size of the metal compound-containing material according to Example 1 after 7 days of production was 625.2 nm by dynamic light scattering method.
[0300] Furthermore, the metal compound-containing material according to Example 1 was applied to the entire surface of a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) using a brush (application amount: 0.0075 g). Next, the carbon substrate to which the metal compound-containing material according to Example 1 was applied was placed in an electric furnace and dried for 10 minutes in the electric furnace heated to 110°C. Thereafter, it was heated for 1 hour in an electric furnace heated to 1500°C under an Ar atmosphere. Then, it was cooled to room temperature to obtain a coated structure according to Example 1.
[0301] The carbon substrate used in Example 1 was an extrusion-molded carbon substrate (a graphite flat plate extrusion material, manufactured by Tokyo Tanso Kogyo Co., Ltd.), but is not limited to extrusion molding.
[0302] Example 2 The metal compound-containing material according to Example 2 is the same as the metal compound-containing material according to Example 1, and therefore a detailed description thereof will be omitted.
[0303] Further, the metal compound-containing material according to Example 2 was applied to the entire surface of a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) using a brush. Next, the carbon substrate to which the metal compound-containing material according to Example 2 was applied was placed in an electric furnace and dried for 10 minutes in an electric furnace heated to 110°C. The metal compound-containing material according to Example 2 was again applied to the entire surface of the dried carbon substrate using a brush, and then the process of drying for 10 minutes in an electric furnace heated to 110°C was repeated two more times. That is, the process of applying the metal compound-containing material according to Example 2 to the carbon substrate and drying was repeated three times in total (total amount of application for all three times was 0.0225 g). Then, the carbon substrate was heated for 1 hour in an electric furnace heated to 1500°C under an Ar atmosphere. Then, the coated structure according to Example 2 was obtained by cooling to room temperature.
[0304] Moreover, the carbon substrate used in Example 2 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0305] Example 3 The metal compound-containing material according to Example 3 was obtained as follows: 137.9 g of tantalum hydroxide (Ta2O5 concentration 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of 55 mass% hydrofluoric acid aqueous solution, and 849 mL of ion-exchanged water was added to obtain a tantalum fluoride aqueous solution (Ta2O5 concentration 8.2 mass%).
[0306] 27.5 g of hydrogen peroxide solution (H2O2 concentration 35 mass %) was added to 1,000 g of this tantalum fluoride aqueous solution (H2O2 / Ta molar ratio = 0.76) and stirred for 5 minutes to obtain an aqueous tantalum compound solution.
[0307] 1,000 g of this tantalum compound aqueous solution was added to 6.82 L of ammonia water (NH3 concentration 25 mass %) in less than 10 minutes (NH3 / Ta molar ratio = 245, NH3 / HF molar ratio = 30.7) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of tantalic acid compound hydrate, in other words, a slurry of tantalum-containing precipitate.
[0308] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed, using aqueous ammonia as the washing liquid.
[0309] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 concentration in the tantalum-containing precipitate slurry was calculated from its weight.
[0310] Then, the tantalum-containing precipitate slurry diluted with pure water, 5 mass% dimethylamine as an organic nitrogen compound, and pure water were mixed so that the tantalum concentration of the final mixture was 5 mass% in terms of Ta2O5 and the weight ratio of Ta2O5 / organic nitrogen compound was 1.0, to obtain an aqueous tantalic acid solution. The initial pH of the aqueous tantalic acid solution was 12.0.
[0311] A neutralized salt of a polyolefin-based polymer-based copolymer (Zaixen A manufactured by Sumitomo Seika Chemicals) was added to the obtained tantalic acid aqueous solution, and the mixture was stirred at 25°C for 30 minutes to obtain a tantalic acid aqueous solution (containing a resin) as a metal compound-containing material according to Example 3. The tantalum concentration of the tantalic acid aqueous solution (containing a resin) as the metal compound-containing material according to Example 3 was 5% in terms of Ta2O5 and 4.1% in terms of Ta. The content of the resin component contained in the metal compound-containing material according to Example 3 was 0.025% by mass when the metal compound-containing material was taken as 100% by mass.
[0312] The amount of the neutralized salt of the polyolefin-based polymer copolymer added here was measured so that, when the total amount of the neutralized salt of the polyolefin-based polymer copolymer was taken as 100% by mass, the resin component was 25% by mass, ammonia water was less than 1% by mass, and the remainder was pure water.
[0313] Furthermore, the metal compound-containing material of Example 3 was applied to the entire surface of a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) using a brush (application amount: 0.0075 g), and a coated structure of Example 3 was obtained in the same manner as in Example 1.
[0314] Moreover, the carbon substrate used in Example 3 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0315] Example 4 The metal compound-containing material according to Example 4 is the same as the metal compound-containing material according to Example 3, and therefore a detailed description thereof will be omitted.
[0316] The metal compound-containing material according to Example 4 was applied to the entire surface of a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) using a brush. Next, the carbon substrate to which the metal compound-containing material according to Example 4 was applied was placed in an electric furnace and dried for 10 minutes in an electric furnace heated to 110°C. The metal compound-containing material according to Example 4 was again applied to the entire surface of the dried carbon substrate using a brush, and then the process of drying for 10 minutes in an electric furnace heated to 110°C was repeated two more times. That is, the process of applying the metal compound-containing material according to Example 4 to the carbon substrate and drying was repeated three times in total (total amount of application for all three times was 0.0225 g). Then, the carbon substrate was heated for 1 hour in an electric furnace heated to 1500°C under an Ar atmosphere. Then, the carbon substrate was cooled to room temperature to obtain a coating structure according to Example 4.
[0317] Moreover, the carbon substrate used in Example 4 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0318] Example 5 The metal compound-containing material according to Example 5 was obtained as follows: 100 g of tantalum hydroxide (Ta2O5 concentration 99.9 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 100 g of 55 mass% hydrofluoric acid aqueous solution, and 100 mL of ion-exchanged water was added to obtain a tantalum fluoride aqueous solution (Ta2O5 concentration 33.3 mass%).
[0319] To 100 g of this tantalum fluoride aqueous solution, 1000 mL of ammonia water (NH3 concentration: 25 mass %) was added to obtain a fluorine-containing tantalum hydrate cake.
[0320] Next, this fluorine-containing tantalum hydrate cake was decanted using a centrifuge and washed with dilute ammonia water until the amount of liberated fluoride ions was 100 mg / L or less, thereby obtaining a tantalum-containing precipitate from which the fluoride ions had been removed. At this time, ammonia water was used as the washing liquid.
[0321] Here, the tantalum concentration of the obtained tantalum-containing precipitate was measured by taking a part of the tantalum-containing precipitate, drying it at 110°C for 24 hours, and then firing it at 1000°C for 4 hours to generate Ta2O5. The weight of the Ta2O5 thus generated was measured, and the Ta2O5 (tantalum oxide, oxide equivalent) concentration of the tantalum-containing precipitate calculated from the weight was 50 mass%. In addition, the Ta (tantalum, metal equivalent) concentration of the tantalum-containing precipitate was calculated to be 40.9 mass%.
[0322] Then, 50g of 10% by mass triethylamine and 317g of pure water were added to the obtained tantalum-containing precipitate, and the mixture was stirred for 10 minutes to obtain a tantalum-containing mixed solution. After that, 83g of 35% by mass hydrogen peroxide was added to the tantalum-containing mixed solution so that the final tantalum concentration was 5% by mass in terms of oxide (Ta2O5), 4.1% by mass in terms of metal (Ta), and the final hydrogen peroxide concentration was 6.8% by mass, and the mixture was stirred for 30 minutes to obtain a tantalic acid compound-containing solution as a metal compound-containing material according to Example 5. Here, the tantalum concentration of the tantalic acid compound-containing solution, which is the metal compound-containing material according to Example 5, was 5% in terms of Ta2O5 and 4.1% in terms of Ta. No precipitate or sediment was observed in the metal compound-containing material according to Example 5. The initial pH of the metal compound-containing material according to Example 5 was 11.0.
[0323] The metal compound-containing material of Example 5 was applied to the entire surface of a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) using a brush (application amount: 0.0075 g), and a coated structure of Example 5 was obtained in the same manner as in Example 1.
[0324] Moreover, the carbon substrate used in Example 5 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0325] Example 6 The metal compound-containing material according to Example 6 was obtained as follows. A polyolefin-based polymer-based copolymer neutralization salt (Zaixen A manufactured by Sumitomo Seika Chemicals) was added to the metal compound-containing material according to Example 5, and the mixture was stirred at 25° C. for 30 minutes to obtain a tantalic acid compound-containing liquid (containing resin) as the metal compound-containing material according to Example 6. Here, the tantalum concentration of the tantalic acid compound-containing liquid (containing resin), which is the metal compound-containing material according to Example 6, was 5% in terms of Ta2O5 and 4.1% in terms of Ta. The content of the resin component contained in the tantalic acid compound-containing liquid (containing resin) used in Example 6 was 0.025% by mass when the tantalic acid compound-containing liquid (containing resin) was 100% by mass.
[0326] The polyolefin-based polymer copolymer neutralization salt added in Example 6 was the same as the polyolefin-based polymer copolymer neutralization salt used in Example 3, so a detailed description thereof will be omitted.
[0327] The metal compound-containing material of Example 6 was applied to the entire surface of a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) using a brush (application amount: 0.0075 g), and a coated structure of Example 6 was obtained in the same manner as in Example 1.
[0328] Moreover, the carbon substrate used in Example 6 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0329] Example 7 The metal compound-containing material of Example 7 was obtained by carrying out the same manufacturing method as Example 1, except that the tantalum concentration of the tantalum peroxocitrate solution was 1% in terms of Ta2O5, and was adjusted to 0.8% in terms of Ta.
[0330] In addition, the metal compound-containing material of Example 7 was applied to the entire surface of a carbon substrate (length x width x thickness: 25 mm x 25 mm x 3 mm) using a brush (application amount: 0.054 g), and a coated structure of Example 7 was obtained in the same manner as in Example 1.
[0331] On the other hand, the carbon substrate used in Example 7 was the same as that used in Example 1, except that its length×width×thickness dimensions were 25 mm×25 mm×3 mm.
[0332] Example 8 The metal compound-containing material of Example 8 was obtained by carrying out the same manufacturing method as in Example 1, except that the tantalum concentration of the tantalum peroxocitrate solution was 5% in terms of Ta2O5, and was adjusted to 4.1% in terms of Ta.
[0333] In addition, the metal compound-containing material of Example 8 was applied to the entire surface of a carbon substrate (length x width x thickness: 25 mm x 25 mm x 3 mm) using a brush (application amount: 0.113 g), and a coated structure of Example 8 was obtained in the same manner as in Example 1.
[0334] On the other hand, the carbon substrate used in Example 8 was the same as that used in Example 7, and therefore a detailed description thereof will be omitted.
[0335] Example 9 The metal compound-containing material of Example 9 was obtained by carrying out the same manufacturing method as in Example 1, except that the tantalum concentration of the tantalum peroxocitrate solution was 20% in terms of Ta2O5, and was adjusted to 16.4% in terms of Ta.
[0336] In addition, the metal compound-containing material of Example 9 was applied to the entire surface of a carbon substrate (length x width x thickness: 25 mm x 25 mm x 3 mm) using a brush (application amount: 0.174 g), and a coated structure of Example 9 was obtained in the same manner as in Example 1.
[0337] On the other hand, the carbon substrate used in Example 9 was the same as that used in Example 7, and therefore a detailed description thereof will be omitted.
[0338] Example 10 The metal compound-containing material of Example 10 was obtained by carrying out the same manufacturing method as in Example 1, except that the tantalum concentration of the tantalum peroxocitrate solution was 20% in terms of Ta2O5, and was adjusted to 16.4% in terms of Ta.
[0339] In addition, the metal compound-containing material of Example 10 was applied to the entire surface of a carbon substrate (length x width x thickness: 25 mm x 25 mm x 3 mm) using a brush (application amount: 0.2 g), and a coated structure of Example 10 was obtained in the same manner as in Example 1.
[0340] On the other hand, the carbon substrate used in Example 10 was the same as that used in Example 7, except that it was a CIP material (a graphite flat plate CIP material, manufactured by Tokyo Tanso Kogyo Co., Ltd.).
[0341] Example 11 Example 11 was obtained by carrying out a manufacturing method similar to that of Example 3, except that the tantalum concentration of the tantalic acid aqueous solution (containing resin), which is the metal compound-containing material of Example 11, was 1% in terms of Ta2O5 and was adjusted to 0.8% in terms of Ta.
[0342] The polyolefin-based polymer copolymer neutralization salt added in Example 11 was the same as the polyolefin-based polymer copolymer neutralization salt used in Example 3, so a detailed description thereof will be omitted.
[0343] In addition, the metal compound-containing material of Example 11 was applied to the entire surface of a carbon substrate (length x width x thickness: 25 mm x 25 mm x 10 mm) using a brush (application amount: 3.04 g), and a coated structure of Example 11 was obtained in the same manner as in Example 1.
[0344] On the other hand, the carbon substrate used in Example 11 was a heat insulating material (Kureka Felt GF-210, manufactured by Kureha Corporation).
[0345] Example 12 A tantalum peroxocitrate solution (containing a surfactant), which is a metal compound-containing material according to Example 12, was obtained as follows.
[0346] 200g of tantalum hydroxide and 92g of 25% by mass ammonia water were mixed and stirred for 10 minutes to obtain a first mixed solution. Then, 220g of 35% by mass hydrogen peroxide water was further added to the first mixed solution and stirred for 10 minutes to obtain a second mixed solution. Then, 79g of citric acid was added to the second mixed solution and stirred for 10 minutes to obtain a tantalum peroxocitrate solution.
[0347] A surfactant was added to the obtained tantalum peroxocitrate solution, and the solution was stirred at 25° C. for 30 minutes to obtain a tantalum peroxocitrate solution (containing a surfactant) used in Example 12. The tantalum concentration of the tantalum peroxocitrate solution (containing a surfactant) used in Example 12 was 1% in terms of Ta2O5 and 0.8% in terms of Ta. The content of the surfactant contained in the tantalum peroxocitrate solution (containing a surfactant) used in Example 12 was 0.025% by mass when the tantalum peroxocitrate solution was taken as 100% by mass.
[0348] The surfactant added here is a polyoxyethylene-added acetylene glycol surfactant.
[0349] In addition, the metal compound-containing material of Example 12 was applied to the entire surface of a carbon substrate (length x width x thickness: 25 mm x 25 mm x 10 mm) using a brush (application amount: 1.99 g), and a coated structure of Example 12 was obtained in the same manner as in Example 1.
[0350] On the other hand, the carbon substrate used in Example 12 was the same as that used in Example 11, and therefore a detailed description thereof will be omitted.
[0351] Example 13 The tantalum peroxocitrate solution (containing a surfactant), which is a metal compound-containing material of Example 13, was obtained by carrying out a manufacturing method similar to that of Example 12, except that the tantalum concentration of the tantalum peroxocitrate solution (containing a surfactant) was 5% in terms of Ta2O5, and was adjusted to 4.1% in terms of Ta.
[0352] In addition, the metal compound-containing material of Example 13 was applied to the entire surface of a carbon substrate (length x width x thickness: 25 mm x 25 mm x 10 mm) using a brush (application amount: 2.22 g), and a coated structure of Example 13 was obtained in the same manner as in Example 1.
[0353] On the other hand, the carbon substrate used in Example 13 was the same as that used in Example 11, and therefore a detailed description thereof will be omitted.
[0354] Example 14 The tantalum peroxocitrate solution (containing a surfactant), which is a metal compound-containing material of Example 14, was obtained by carrying out a manufacturing method similar to that of Example 12, except that the tantalum concentration of the tantalum peroxocitrate solution (containing a surfactant) was 5% in terms of Ta2O5, and was adjusted to 4.1% in terms of Ta.
[0355] In addition, the metal compound-containing material of Example 14 was applied to the entire surface of a carbon substrate (length x width: 50 mm x 50 mm) using a brush (application amount: 0.44 g), and a coated structure of Example 14 was obtained in the same manner as in Example 1.
[0356] On the other hand, the carbon substrate used in Example 14 was cloth (MUTEKI carbon cloth carbon (carbon fiber) manufactured by MUGE).
[0357] Example 15 The tantalum peroxocitrate solution, which is the metal compound-containing material according to Example 15, is the same as the tantalum peroxocitrate solution according to Example 8, and therefore a detailed description thereof will be omitted.
[0358] In addition, the metal compound-containing material of Example 15 was applied to the entire surface of a carbon substrate (length x width: 50 mm x 50 mm) using a brush (application amount: 0.34 g), and a coated structure of Example 15 was obtained in the same manner as in Example 1.
[0359] On the other hand, the carbon substrate used in Example 15 was the same as that used in Example 14, and therefore a detailed description thereof will be omitted.
[0360] (Example 16) The tantalum peroxocitrate solution, which is the metal compound-containing material according to Example 16, is the same as the tantalum peroxocitrate solution according to Example 9, and therefore a detailed description thereof will be omitted.
[0361] In addition, the metal compound-containing material of Example 16 was applied to the entire surface of a carbon substrate (length x width: 50 mm x 50 mm) using a brush (application amount: 0.75 g), and a coated structure of Example 16 was obtained in the same manner as in Example 1.
[0362] On the other hand, the carbon substrate used in Example 16 was the same as that used in Example 14, and therefore a detailed description thereof will be omitted.
[0363] (Example 17) The metal acid compound mixture of Example 17, which is a metal compound-containing material, is a mixture prepared by adjusting the content of each of an aqueous tantalic acid solution, an aqueous niobic acid solution, an aqueous titanic acid solution, and an aqueous zirconium solution to 1%, and each of an aqueous hafnic acid solution and an aqueous silicic acid solution to 0.2%, when the aqueous metal acid compound mixture is taken as 100%. The aqueous metal acid compound mixture of Example 17 was obtained as follows.
[0364] The tantalic acid aqueous solution contained in the metal acid compound mixed liquid of Example 17 was obtained in the same manner as the tantalic acid aqueous solution which is the metal compound-containing material of Example 3.
[0365] The aqueous niobic acid solution used in Example 17 was prepared as follows.
[0366] 100 g of niobium pentoxide was dissolved in 200 g of a 55 mass % aqueous solution of hydrofluoric acid, and 830 mL of ion-exchanged water was added to obtain an aqueous solution of niobium fluoride (Nb2O5=8.84 mass %).
[0367] 200 mL of this niobium fluoride aqueous solution was added to 1 L of ammonia water (NH3 concentration 25 mass%) in less than 1 minute (NH3 / Nb2O5 molar ratio = 177.9, NH3 / HF molar ratio = 12.2) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of niobium acid compound hydrate, in other words, a slurry of niobium-containing precipitates.
[0368] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less to obtain a niobium-containing precipitate from which the fluoride ions had been removed. At this time, ammonia water was used as the washing liquid.
[0369] Furthermore, the niobium-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a slurry. A portion of this niobium-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1000°C for 4 hours to produce Nb2O5, and the Nb2O5 concentration in the niobium-containing precipitate slurry was calculated from its weight.
[0370] Then, pure water was added to the niobium-containing precipitate slurry diluted with pure water, and a 50 mass% aqueous dimethylamine solution was added as an organic nitrogen compound so that the dimethylamine concentration was 7.2 mass%, thereby adjusting the Nb2O5 solid concentration to 24.0 mass%. This slurry was stirred for 48 hours to obtain the aqueous niobic acid solution used in Example 17. The pH of the aqueous niobic acid solution used in Example 17 was 11.0.
[0371] The titanic acid aqueous solution used in Example 17 was prepared as follows.
[0372] 33.3 g of titanyl sulfate (manufactured by Teika Corporation, TiO2 concentration 33.3 mass%, sulfuric acid concentration 51.1 mass%) was added to 66.7 g of ion-exchanged water and allowed to stand at 90°C or higher for 1 hour to dissolve, obtaining an aqueous titanyl sulfate solution (titanium concentration (TiO2 equivalent) 11 mass%, sulfuric acid 17 mass%, pH 1 or less).
[0373] 100g of this titanyl sulfate aqueous solution was added to 100g of 50% by mass dimethylamine (6.4 moles of amine per mole of sulfuric acid in the titanyl sulfate aqueous solution) over a period of less than 1 minute. The mixture was then stirred for 15 minutes to obtain a neutralized reaction solution (pH 12). This neutralized reaction solution was a slurry of titanium-containing material, in other words, a slurry of titanium-containing precipitate.
[0374] Next, the neutralized reaction solution was decanted using a centrifuge and washed until the sulfuric acid content of the supernatant was 100 mg / L or less, to obtain a titanium-containing precipitate from which sulfuric acid had been removed. At this time, ammonia water was used as the washing liquid.
[0375] A portion of this titanium-containing precipitate was calcined at 1,000°C for 4 hours to generate TiO2, and the TiO2 concentration in the titanium-containing precipitate was calculated from the mass of the TiO2. The TiO2 concentration was 11.0 mass%.
[0376] Then, 45 g of this titanium-containing precipitate was mixed with 5 g of tetramethylammonium hydroxide pentahydrate (TMAH concentration 50% by mass) (0.443 mol per mol of Ti in the titanium-containing precipitate), and the mixture was shaken for 24 hours with a paint shaker to obtain the titanic acid aqueous solution used in Example 12. Here, the titanium concentration of the titanic acid aqueous solution used in Example 17 was 8% in terms of TiO2 and 4.8% in terms of Ti. The pH of the titanic acid aqueous solution used in Example 17 was 13.7.
[0377] The aqueous zirconate solution used in Example 17 was prepared as follows.
[0378] 3.01 g (0.01 mol) of zirconium sulfate monohydrate was dissolved in 2.50 g (0.014 mol) of 55 mass% aqueous sulfuric acid solution, and 25 g of ion-exchanged water and 2.5 g (0.026 mol) of 35 mass% aqueous hydrogen peroxide solution were added (H2O2 / ZrO2 molar ratio = 2.6), to obtain an aqueous zirconium sulfate solution containing 4.3 mass% zirconium in terms of ZrO2.
[0379] Next, the entire amount of the zirconium sulfate aqueous solution was added to 100 g (1.47 mol) of ammonia water (NH3 concentration 25 mass%) in less than 1 minute (NH3 / ZrO2 molar ratio = 147, NH3 / SO4 2- The reaction solution was a slurry of zirconium oxide hydrate, in other words, a slurry of zirconium-containing precipitate.
[0380] The reaction solution was decanted using a centrifuge and washed until the electrical conductivity was 500 μS / cm or less to obtain a zirconium-containing precipitate from which the sulfur content had been removed. At this time, ammonia water was used as the washing liquid.
[0381] Furthermore, the zirconium-containing precipitate from which the sulfur was removed was diluted with pure water to obtain a zirconium-containing precipitate slurry from which the sulfur was removed. A part of the zirconium-containing precipitate slurry from which the sulfur was removed was dried at 110°C for 24 hours, and then fired at 1,000°C for 4 hours to produce ZrO2, and the ZrO2 concentration in the zirconium-containing precipitate slurry from which the sulfur was removed was calculated from its weight.
[0382] Then, the zirconium-containing precipitate slurry from which the sulfur content was removed and diluted with pure water was mixed with 13.7 g (0.023 mol) of 15% by mass tetramethylammonium hydroxide (TMAH) and 28.5 g of ion-exchanged water so that the zirconium concentration of the final mixture was 10% by mass in terms of ZrO2 and the tetramethylammonium hydroxide (TMAH) concentration was 7.2% by mass (molar ratio of TMAH / ZrO2 = 2.2), and the mixture was stirred and held for 1 hour while maintaining the liquid temperature at room temperature (25 ° C.), to obtain the zirconium acid aqueous solution used in Example 11. Here, the zirconium concentration of the zirconium acid aqueous solution used in Example 17 was 8% in terms of ZrO2 and 5.9% in terms of Zr. The pH of the zirconium acid aqueous solution used in Example 17 was 13.7.
[0383] The aqueous hafnic acid solution used in Example 17 was prepared as follows.
[0384] To 76.0 g of hafnium oxide (98% purity, powder, manufactured by Kojundo Kagaku Kenkyusho Co., Ltd.), 105.1 g of 55% by mass hydrofluoric acid and 796.9 g of pure water were added, and the mixture was heated to 80°C using a water bath and stirred for 24 hours to dissolve the hafnium compound in hydrofluoric acid to obtain a hafnium compound hydrofluoric acid solution. 60 g of this hafnium compound hydrofluoric acid solution was mixed with 2.2 g of 35% by mass hydrogen peroxide to obtain a hafnium complex aqueous solution (H2O2 / Hf molar ratio = 1.0), and after stirring for 5 minutes, the solution was gradually added to 377.2 g of 25% by mass ammonia water (NH3 / Hf molar ratio = 250). After stirring for 5 minutes, a neutralized reaction solution containing hafnium hydroxide was obtained as a precipitate.
[0385] Next, the neutralized reaction liquid was decanted using a centrifuge to recover a precipitate (containing hafnium hydroxide). The recovered precipitate was mixed with 200 g of 25% by mass ammonia water to form a slurry, and then decanted again to recover the precipitate. This decantation and recovery process of the precipitate (containing hafnium hydroxide) was repeated three times.
[0386] Then, 31.1 g of 25 mass% TMAH was added to the collected precipitate (containing hafnium hydroxide) to obtain a mixed solution. Pure water was added to the mixed solution until the total weight of the mixed solution reached 77.7 g so that the final hafnium concentration was 6 mass% in terms of HfO2, and the mixed solution was stirred for 6 hours to obtain the hafnium acid aqueous solution used in Example 17. The pH of the hafnium acid aqueous solution used in Example 17 was 14.8.
[0387] The aqueous silicic acid solution used in Example 17 was obtained as follows.
[0388] In a 100 mL beaker, 11.0 g of tetraethoxysilane (TEOS, manufactured by Tokyo Ohka Kogyo Co., Ltd.), which is a silicon-containing raw material, was added with 0.1 g of acetic acid (manufactured by Hayashi Pure Chemical Industries, Ltd.), which is an acidic aqueous solution, 15 g of industrial ethanol (Solmix AP-7 (a mixed alcohol solvent containing 85.5 mass% ethanol, 9.6 mass% 1-propanol, 4.9 mass% 2-propanol, and 0.2 mass% or less water), manufactured by Toyo Petrochemical Co., Ltd.), and 8 g of pure water, and the mixture was mixed at room temperature (25° C.) for 20 hours while stirring with a stirrer tip, to obtain 6 g of a dried silicon compound, which was a transparent precipitate.
[0389] Next, 2.6 g of 40% by mass methylamine (manufactured by Mitsubishi Gas Chemical Company, Inc.) and 8.9 g of pure water were added to 6 g of the obtained dried silicon compound, and the mixture was mixed for 10 hours at room temperature (25°C) while stirring with a stirrer tip to obtain the aqueous silicic acid solution used in Example 17.
[0390] The thus obtained tantalic acid aqueous solution, niobic acid aqueous solution, titanic acid aqueous solution, zirconium aqueous solution, hafnic acid aqueous solution, and silicic acid aqueous solution were adjusted to 1% each of the tantalic acid aqueous solution, niobic acid aqueous solution, titanic acid aqueous solution, and zirconium aqueous solution, and 0.2% each of the hafnic acid aqueous solution and silicic acid aqueous solution, when the metal acid compound mixed solution of Example 17 was taken as 100%, to obtain the metal acid compound mixed solution of Example 17.
[0391] In addition, the metal compound-containing material of Example 17 was applied to the entire surface of a carbon substrate (length x width: 50 mm x 50 mm) using a brush (application amount: 0.5 g), and a coated structure of Example 17 was obtained in the same manner as in Example 1.
[0392] On the other hand, the carbon substrate used in Example 17 was the same as that used in Example 14, and therefore a detailed description thereof will be omitted.
[0393] (Example 18) The zirconate aqueous solution which is the metal compound-containing material according to Example 18 is the same as the zirconate aqueous solution contained in the metal compound-containing material according to Example 17, and therefore a detailed description thereof will be omitted.
[0394] In Example 18, a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) was immersed in a 50 mL beaker in an aqueous zirconium acid solution (about 10 ml), and the aqueous zirconium acid solution was impregnated into the carbon substrate under reduced pressure conditions (so-called vacuum impregnation) (impregnated amount: 0.98 g). Next, the carbon substrate impregnated with the aqueous zirconium acid solution was placed in an electric furnace and dried for 60 minutes in an electric furnace heated to 100°C. Thereafter, the carbon substrate was heated for 1 hour in an electric furnace heated to 1500°C under an Ar atmosphere. Then, the carbon substrate was cooled to room temperature to obtain a coating structure according to Example 18.
[0395] On the other hand, the carbon substrate used in Example 18 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0396] (Example 19) The titanic acid aqueous solution which is the metal compound-containing material of Example 19 is the same as the titanic acid aqueous solution contained in the metal compound-containing material of Example 17, and therefore a detailed description thereof will be omitted.
[0397] In Example 19, a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) was immersed in a titanic acid aqueous solution (about 10 ml) in a 50 mL beaker, and the titanic acid aqueous solution was impregnated into the carbon substrate under reduced pressure conditions (impregnated amount: 0.96 g). Next, the carbon substrate impregnated with the titanic acid aqueous solution was placed in an electric furnace and dried for 60 minutes in the electric furnace heated to 100°C. Thereafter, the carbon substrate was heated for 1 hour in an electric furnace heated to 1500°C under an Ar atmosphere. Then, the carbon substrate was cooled to room temperature to obtain a coating structure according to Example 19.
[0398] On the other hand, the carbon substrate used in Example 19 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0399] Comparative Example 1 A polyolefin-based polymer copolymer neutralization salt (Zaixen A manufactured by Sumitomo Seika Chemicals) was applied to the entire surface of a carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) using a brush. Next, the carbon substrate coated with the polyolefin-based polymer copolymer neutralization salt was placed in an electric furnace and dried for 10 minutes in the electric furnace heated to 110°C. After that, it was heated for 1 hour in an electric furnace heated to 1500°C under an Ar atmosphere. Then, it was cooled to room temperature to obtain a coated structure according to Comparative Example 1.
[0400] The polyolefin-based polymer copolymer neutralized salt used in Comparative Example 1 was the same as the polyolefin-based polymer copolymer neutralized salt used in Example 3, and therefore a detailed description thereof will be omitted.
[0401] On the other hand, the carbon substrate used in Comparative Example 1 was the same as that used in Example 1, and therefore a detailed description thereof will be omitted.
[0402] (Reference example 1) Reference Example 1 is a carbon substrate in which the surface of an extruded carbon substrate (length x width x thickness: 50 mm x 50 mm x 3 mm) is processed by repeatedly discharging the surface using a discharge electrode made of tantalum. Comparative Example 3 Since the carbon substrate used in Comparative Example 3 is the same as that used in Example 7, a detailed description thereof will be omitted.
[0403] Comparative Example 4 Since the carbon substrate used in Comparative Example 4 is the same as that used in Example 10, a detailed description thereof will be omitted.
[0404] Comparative Example 5 Since the carbon substrate used in Comparative Example 5 is the same as that used in Example 11, a detailed description thereof will be omitted.
[0405] Comparative Example 6 Since the carbon substrate used in Comparative Example 6 is the same as that used in Example 14, a detailed description thereof will be omitted.
[0406] Comparative Example 7 Since the carbon substrate of Comparative Example 7 is the same as that used in Example 1, a detailed description thereof will be omitted.
[0407] Among the metal compound-containing materials according to the embodiment of the present invention, those containing a resin will be described with reference to the following experimental examples, although the present invention is not limited to these experimental examples.
[0408] (Experimental Example 1) In experimental example 1, a niobic acid-containing liquid having a particle size D50 of 5 nm or less as measured by particle size distribution measurement using dynamic light scattering, a niobium concentration of 7.0 mass% in metal equivalent (Nb equivalent), and a solvent of pure water was used as the metal acid compound, and an anionic acrylic resin (J-127 manufactured by Arakawa Chemical Co., Ltd.) was used as the resin solid, and these were weighed out so that the metal acid compound content / (resin solid content+metal acid compound content)=0.70 and the resin solid content+metal acid compound content=0.05 were satisfied, and the metal acid compound-containing liquid of experimental example 1 was obtained by mixing and stirring these.
[0409] Specifically, when the metal acid compound-containing liquid of Experimental Example 1 was taken as 100 mass%, the following ingredients were weighed out so that the niobium concentration was 2.45 mass% in metal equivalent (Nb equivalent), anionic acrylic resin (J-127 manufactured by Arakawa Chemical Co., Ltd.), 1.5 mass% methylamine, 0.7 mass% and the remainder was pure water, and these were mixed and stirred at 25°C for 30 minutes to obtain the metal acid compound-containing liquid of Experimental Example 1.
[0410] (Experimental Example 2) In experimental example 2, a manufacturing method similar to that of experimental example 1 was carried out, except that the anionic acrylic resin (manufactured by Arakawa Chemical Industries, Ltd.: J-127) in experimental example 1 was replaced with an anionic acrylic resin (manufactured by Arakawa Chemical Industries, Ltd.: WC-M-1212), to obtain a metal acid compound-containing liquid according to experimental example 2.
[0411] (Experimental Example 3) In Experimental Example 3, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with an acrylic resin (Toyochem Co., Ltd.: Tocryl X-4402), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid according to Experimental Example 3.
[0412] (Experimental Example 4) In Experimental Example 4, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with an acrylic resin (Toyochem Co., Ltd.: Tocryl X-4403), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 4.
[0413] (Experimental Example 5) In experimental example 5, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in experimental example 1 was replaced with an anionic styrene-based resin (WC-M-1216 manufactured by Arakawa Chemical Industries, Ltd.), and a manufacturing method similar to that of experimental example 1 was carried out to obtain a metal acid compound-containing liquid according to experimental example 5.
[0414] (Experimental Example 6) In Experimental Example 6, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with an anionic olefin resin (WC-M-1201 manufactured by Arakawa Chemical Industries, Ltd.), and a manufacturing method similar to that of Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid according to Experimental Example 6.
[0415] (Experimental Example 7) In experimental example 7, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in experimental example 1 was replaced with a nonionic copolymer polyamide resin (Sepoljon PA200 manufactured by Sumitomo Seika Chemicals Co., Ltd.), and a manufacturing method similar to that of experimental example 1 was carried out to obtain a metal acid compound-containing liquid for experimental example 7.
[0416] (Experimental Example 8) In experimental example 8, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in experimental example 1 was replaced with a nonionic copolymer polyamide resin (Sepoljon PA150 manufactured by Sumitomo Seika Chemicals Co., Ltd.), and a manufacturing method similar to that of experimental example 1 was carried out to obtain a metal acid compound-containing liquid according to experimental example 8.
[0417] (Experimental Example 9) In Experimental Example 9, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a nonionic polyamide elastomer resin (Sepoljon NE205N manufactured by Sumitomo Seika Chemicals Co., Ltd.), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 9.
[0418] (Experimental Example 10) In Experimental Example 10, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a styrene acrylic resin (Toyochem Co., Ltd.: Tocryl BCX-3101), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 10.
[0419] (Experimental Example 11) In Experimental Example 11, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Co., Ltd.) in Experimental Example 1 was replaced with a styrene acrylic resin (Toyochem Co., Ltd.: Tocryl W-172), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 11.
[0420] (Experimental Example 12) In Experimental Example 12, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a styrene acrylic resin (Tocryl W-463 manufactured by Toyochem Co., Ltd.), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 12.
[0421] (Experimental Example 13) In Experimental Example 13, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a styrene acrylic resin (Tocryl M-4340 manufactured by Toyochem Co., Ltd.), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 13.
[0422] (Experimental Example 14) In experimental example 14, the same manufacturing method as in experimental example 1 was carried out, except that the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in experimental example 1 was replaced with an anionic ethylene-acrylic acid copolymer ammonium salt resin (Zaixen AC manufactured by Sumitomo Seika Chemicals Co., Ltd.), to obtain a metal acid compound-containing liquid for experimental example 14.
[0423] (Experimental Example 15) In Experimental Example 15, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a nonionic ethylene-acrylic acid copolymer resin (Zaixen A manufactured by Sumitomo Seika Chemicals Co., Ltd.), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 15.
[0424] (Experimental Example 16) In Experimental Example 16, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a nonionic ethylene-acrylic acid copolymer resin (Zaixen AC-HW-10 manufactured by Sumitomo Seika Chemicals Co., Ltd.), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 16.
[0425] (Experimental Example 17) In Experimental Example 17, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a nonionic carboxyl group-containing polyethylene resin (Zaixen L manufactured by Sumitomo Seika Chemicals Co., Ltd.), and a manufacturing method similar to that of Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid according to Experimental Example 17.
[0426] (Experimental Example 18) In Experimental Example 18, the anionic acrylic resin (J-127 manufactured by Arakawa Chemical Industries, Ltd.) in Experimental Example 1 was replaced with a polysiloxane-acrylic resin (Ceranet WHW-822 manufactured by DIC Corporation), and the same manufacturing method as in Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid for Experimental Example 18.
[0427] (Experimental Example 19) In Experimental Example 19, the niobic acid-containing liquid of Experimental Example 1 was replaced with a niobic acid-containing liquid, a tantalic acid-containing liquid, a titanic acid-containing liquid, a molybdic acid-containing liquid, and a tungstic acid-containing liquid, each of which had a particle size D50 of 5 nm or less as measured by dynamic light scattering particle size distribution measurement, a metal element concentration (niobium concentration, tantalum concentration, titanium concentration, molybdenum concentration, and tungsten concentration) of 7.0 mass% in terms of metal (Nb conversion, Ta conversion, Ti conversion, Mo conversion, and W conversion), and the solvent was pure water. A zirconium acid-containing liquid having a particle size D50 of 100 nm or less as measured by dynamic light scattering particle size distribution, a zirconium concentration of 7.0 mass% in metal equivalent (Zr equivalent), and a solvent of pure water was replaced with a metal acid mixed liquid containing equivalent amounts in a metal equivalent weight ratio, and 0.7 mass% methylamine was replaced with 0.7 mass% TMAH as the organic nitrogen compound. A manufacturing method similar to that of Experimental Example 1 was carried out to obtain a metal acid compound-containing liquid of Experimental Example 19.
[0428] Comparative Example 2 In Comparative Example 2, a niobium acid-containing liquid having a particle size D50 of 5 nm or less as measured by particle size distribution using dynamic light scattering, a niobium concentration of 7.0 mass% in metal equivalent (Nb equivalent), and pure water as a solvent was weighed out so that, when the metal acid compound-containing liquid of Comparative Example 2 was 100 mass%, the niobium concentration was 2.45 mass% in metal equivalent (Nb equivalent), methylamine was 0.7 mass%, and the remainder was pure water. These were mixed and stirred at 25°C for 30 minutes to obtain the metal acid compound-containing liquid of Comparative Example 2.
[0429] The following physical property values were measured and evaluation tests were performed for the metal compound-containing materials according to Examples 1 to 19, the metal acid compound-containing liquids according to Experimental Examples 1 to 19, the coated structure according to Comparative Example 1, the carbon substrates according to Reference Example 1 and Comparative Examples 3 to 7, and the metal acid compound-containing liquid according to Comparative Example 2. The physical property values of the metal compound-containing materials according to Examples 1 to 10, the coated structure according to Comparative Example 1, and the carbon substrates according to Reference Example 1 and Comparative Examples 3 and 4 are shown in FIG. 1. The physical property values of the metal compound-containing materials according to Examples 11 to 17 and the carbon substrates according to Comparative Examples 5 and 6 are shown in FIG. 2. Furthermore, the physical property values of the metal compound-containing materials according to Examples 18 and 19 and the carbon substrate according to Comparative Example 7 are shown in FIG. 3.
[0430] Fig. 4 shows a table listing the physical properties of the metallic acid compound-containing liquids according to Experimental Examples 1 to 19 of the present invention and Comparative Example 2. Fig. 5 shows a table listing the measurement results of the metallic acid compound-containing liquids according to Experimental Examples 1 to 19 of the present invention and Comparative Example 2. Fig. 6 shows the physical properties and measurement results of the metallic acid compound-containing liquids according to Experimental Examples 2 to 6, 13, 15, and 17 to 19 of the present invention and Comparative Example 2.
[0431] <Elemental analysis> If necessary, the sample was appropriately diluted with dilute hydrochloric acid, and the mass fraction in terms of metal was measured using ICP emission spectrometry (Agilent Technologies: AG-5110) in accordance with JIS K0116:2014.
[0432] Dynamic Light Scattering The particle size distribution of the metal compound-containing material according to Examples 1 to 19 and the metal acid compound-containing liquid according to Experimental Examples 1 to 19 was evaluated in accordance with JIS Z 8828:2019 "Particle size analysis-Dynamic light scattering method" using a zeta potential / particle size / molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000). In addition, in order to remove dust and the like in the solution to be measured immediately before the measurement, the content was filtered with a filter having a pore size of 2 μm, and ultrasonic treatment was performed for 3 minutes at 28 kHz using an ultrasonic cleaner (manufactured by AS ONE Co., Ltd.: VS-100III). The particle size (D50) refers to the median size (D50), which is the particle size showing the 50% cumulative value of the cumulative distribution curve.
[0433] <Light transmittance measurement> 4 ml of the metal compound-containing materials according to Examples 1 to 19 were placed in a quartz cell with an optical path length of 5.0 mm, and the light transmittance of the metal compound-containing materials according to Examples 1 to 19 in the wavelength range of 500 nm to 700 nm was measured using a spectrophotometer according to the light transmittance measurement conditions described above or the light transmittance measurement conditions (including Si).
[0434] 4 ml of the metal acid compound-containing liquid according to Experimental Examples 1 to 19 and Comparative Example 2 was placed in a quartz cell with an optical path length of 5.0 mm, and the light transmittance in the wavelength range of 550 nm to 700 nm (specifically, the light transmittance at wavelengths of 550 nm, 600 nm, 650 nm, and 700 nm) of the metal acid compound-containing liquid according to Experimental Examples 1 to 19 and Comparative Example 2 was measured using a spectrophotometer according to the transmittance measurement conditions described above. Then, the light transmittance at wavelengths of 550 nm, 600 nm, 650 nm, and 700 nm of 70%T or more was evaluated as "◯ (GOOD)", and the light transmittance less than 70%T was evaluated as "× (BAD)". The "initial light transmittance" in FIG. 5 refers to the light transmittance of the metal acid compound-containing liquid adjusted to a liquid temperature of 25°C immediately after production. Moreover, the "light transmittance over time" in FIG. 5 refers to the light transmittance of the metal acid compound-containing liquid after it was left to stand for one month in an incubator set at room temperature of 25°C.
[0435] <Heat resistance test> The coated structures according to Examples 1 to 19, the coated structure according to Comparative Example 1, and the carbon substrates according to Reference Example 1 and Comparative Examples 3 to 7 were subjected to heat resistance tests under the following three test conditions.
[0436] <Heat resistance test 1> First, the weights of the coated structures according to Examples 1 to 17, the coated structure according to Comparative Example 1, and the carbon substrates according to Reference Example 1 and Comparative Examples 3 to 6 before heat resistance test 1 (hereinafter referred to as weight before test 1) were measured. Next, the coated structures according to Examples 1 to 17, the coated structure according to Comparative Example 1, and the carbon substrates according to Reference Example 1 and Comparative Examples 3 to 6 were placed in a tubular furnace and fired in an air atmosphere at a heating temperature of 700°C for a heating time of 90 minutes. The fired coated structures according to Examples 1 to 17, the coated structure according to Comparative Example 1, and the carbon substrates according to Reference Example 1 and Comparative Examples 3 to 6 were taken out of the tubular furnace and the weights after heat resistance test 1 (hereinafter referred to as weight after test 1) were measured. Then, the weight change (attenuation rate) in heat resistance test 1 was calculated from the weights before test 1 and the weights after test 1 for the coated structures according to Examples 1 to 17, the coated structure according to Comparative Example 1, and the carbon substrates according to Reference Example 1 and Comparative Examples 3 to 6 using the following formula (1).
[0437]
number
[0438] The test results of heat resistance test 1 for the coated structures of Examples 1 to 10, the coated structure of Comparative Example 1, and the carbon substrates of Reference Example 1 and Comparative Examples 3 and 4 are shown in Table 1. The test results of heat resistance test 1 for the coated structures of Examples 11 to 17, and the carbon substrates of Comparative Examples 5 and 6 are shown in Table 2.
[0439] <Heat resistance test 2> The weights of the coated structures according to Examples 5 to 6, the coated structure according to Comparative Example 1, and the carbon substrate according to Reference Example 1 before the heat resistance test 2 (hereinafter referred to as the weight before test 2) were measured. Next, the coated structures according to Examples 5 to 6, the coated structure according to Comparative Example 1, and the carbon substrate according to Reference Example 1 were placed in a tubular furnace and fired at a heating temperature of 700°C for a heating time of 90 minutes in an atmosphere of a 5% by volume O2-95% by volume N2 mixed gas. The fired coated structures according to Examples 5 to 6, the coated structure according to Comparative Example 1, and the carbon substrate according to Reference Example 1 were taken out of the tubular furnace, and the weights after the heat resistance test 2 (hereinafter referred to as the weight after test 2) were measured. Then, the weight change (attenuation rate) in the heat resistance test 2 was calculated from the weights before test 2 and the weights after test 2 for the coated structures according to Examples 5 to 6, the coated structure according to Comparative Example 1, and the carbon substrate according to Reference Example 1 according to the following formula (2).
[0440]
number
[0441] The test results of the heat resistance test 2 for the coated structures of Examples 5 and 6, the coated structure of Comparative Example 1, and the carbon substrate of Reference Example 1 are shown in Table 3.
[0442] <Heat resistance test 3> First, the weights of the coated structures according to Examples 18 and 19 and the carbon substrate according to Comparative Example 7 before the heat resistance test 3 (hereinafter referred to as the weight before test 3) were measured. Next, the coated structures according to Examples 18 and 19 and the carbon substrate according to Comparative Example 7 were placed in a tubular furnace and fired in an air atmosphere at a heating temperature of 600°C for a heating time of 180 minutes. The fired coated structures according to Examples 18 and 19 and the carbon substrate according to Comparative Example 7 were taken out of the tubular furnace and the weights after the heat resistance test 3 (hereinafter referred to as the weight after test 3) were measured. Then, the weight change (attenuation rate) in the heat resistance test 3 was calculated from the weights before test 3 and the weights after test 3 for the coated structures according to Examples 18 and 19 and the carbon substrate according to Comparative Example 7 according to the following formula (3).
[0443]
number
[0444] The test results of the heat resistance test 3 for the coated structures of Examples 18 and 19 and the carbon substrate of Comparative Example 7 are shown in Table 4.
[0445] DLS size compatibility test The initial particle diameters (D50) of particles in the metal acid compound-containing liquids according to Experimental Examples 1 to 19 and Comparative Example 2 were calculated by particle diameter distribution measurement using the dynamic light scattering method described above. Then, particles with an initial particle diameter (D50) of 100 nm or less were evaluated as "〇〇 (VERY GOOD)", particles with an initial particle diameter (D50) of more than 100 nm and less than 3000 nm were evaluated as "〇 (GOOD)", and particles with an initial particle diameter of more than 3000 nm were evaluated as "× (BAD)".
[0446] <DLS diameter stability test> The initial particle size (D50) of particles in the metal acid compound-containing liquid according to Experimental Examples 1 to 19 and Comparative Example 2, and the particle size over time (D50) of particles in the metal acid compound-containing liquid after standing for 20 days in an incubator set at room temperature of 25°C were calculated, and the increase in the particle size over time (D50) relative to the initial particle size (D50) was evaluated as "Good (◯)", and the increase in the particle size over time (D50) was evaluated as "Bad (×)". Note that the above-mentioned filtering was performed when measuring the "initial particle size D50 (nm)", but not when measuring the "particle size over time D50 (nm)", and only ultrasonic treatment was performed.
[0447] <Stability test over time> The metallic acid compound-containing liquids according to Experimental Examples 1 to 19 and Comparative Example 2 were left to stand at room temperature of 25° C. for 20 days, and then the presence or absence of white precipitation and gelation was visually observed. Those in which no white precipitation or gelation was observed were evaluated as having temporal stability and were marked as “◯ (GOOD)”, and those in which even one white precipitation or gelation was observed were evaluated as not having temporal stability and were marked as “× (BAD)”. Here, gelation was judged by placing each metallic acid compound-containing liquid in a plastic container, and turning the container upside down. The dispersion that did not fall quickly was judged to have gelled.
[0448] <pH measurement> The pH of the metal acid compound-containing liquid obtained in Experimental Examples 1 to 19 and Comparative Example 2 was measured using an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) after confirming that the liquid temperature was stabilized at 25°C. "Initial pH" in Fig. 5 refers to the pH of the metal acid compound-containing liquid whose temperature was adjusted to 25°C immediately after production. "pH over time" in Fig. 5 refers to the pH of the metal acid compound-containing liquid after it was left to stand for one month in an incubator set at room temperature of 25°C.
[0449] <Film-forming test (glass)> The appearance of the coating film formed on the surface of the glass substrate, which is a substitute for the current collector plate, was evaluated by observing it with an optical microscope. The metal acid compound-containing liquid of Experimental Examples 1 to 19 and Comparative Example 2 was filtered with a filter having a pore size of 2 μm, and dropped onto a 50 mm×50 mm glass substrate that had been degreased and washed with acetone and then dried using a syringe, and applied by spin coating (1,500 rpm, 15 seconds). The applied portion was then naturally dried to form a coating film on the glass substrate. The glass substrate was observed with an optical microscope (magnification: 40 times) in a central 15 mm×15 mm range of the formed coating film, and a substrate in which no air bubbles, uneven coating, or cracks were observed was evaluated as having excellent film-forming properties and was evaluated as "○ (GOOD)", and a substrate in which even one of the following was observed was evaluated as not having excellent film-forming properties and was evaluated as "× (BAD)" (see FIG. 5).
[0450] <Adhesion test (glass)> A cellophane adhesive tape as specified in JIS Z 1522:2009 was applied to the coating surface on the glass substrate formed in the same manner as in the above-mentioned film-forming test (glass). The cellophane adhesive tape was squeezed from above with a finger, and then quickly peeled off in a direction perpendicular to the coating surface, and the presence or absence of peeling of the coating on the glass substrate was observed. Those in which no peeling of the coating was observed were evaluated as having excellent adhesion and were given a rating of "◯ (GOOD)", and those in which peeling of the coating was observed were evaluated as having poor adhesion and were given a rating of "× (BAD)" (see Figure 5). The samples used in the adhesion test (glass) were those that had been applied for one day.
[0451] <Film-forming test (PET)> The appearance of the coating film formed on the surface of the PET substrate was evaluated by observing it with an optical microscope. The metal acid compound-containing liquid of Experimental Examples 2 to 6, 13, 15, 17 to 19, and Comparative Example 2 was filtered with a filter having a pore size of 2 μm, and dropped onto a 50 mm×50 mm PET substrate that had been degreased and washed with acetone and then dried using a syringe, and applied by spin coating (1,500 rpm, 15 seconds). The applied area was then naturally dried to form a coating film on the PET substrate. The PET substrate was observed with an optical microscope (magnification: 40 times) in a central area of 15 mm×15 mm of the formed coating film. If no air bubbles, uneven coating, or cracks were observed, the substrate was evaluated as having excellent film-forming properties and was evaluated as "○ (GOOD)", and if even one of the following was observed, the substrate was evaluated as not having excellent film-forming properties and was evaluated as "× (BAD)" (see FIG. 6).
[0452] <Adhesion test (PET)> A cellophane adhesive tape as specified in JIS Z 1522:2009 was applied to the coating surface of the PET substrate formed in the same manner as in the above-mentioned film-forming test (PET). The cellophane adhesive tape was squeezed with a finger from above, and then quickly peeled off in a direction perpendicular to the coating surface, and the presence or absence of peeling of the coating on the PET substrate was observed. Those in which no peeling of the coating was observed were evaluated as having excellent adhesion and were rated as "Good (◯)", and those in which peeling of the coating was observed were evaluated as having poor adhesion and were rated as "Bad (×)" (see Figure 6). The samples used in the adhesion test (PET) were those that had been applied for one day.
[0453] [Table 1]
[0454] [Table 2]
[0455] [Table 3]
[0456] [Table 4]
[0457] The coated structures of Examples 1 to 17 have a uniform metal-carbon composite coating on the carbon substrate by applying a metal compound-containing material onto the carbon substrate and heating the carbon substrate to which the metal compound-containing material has been applied.
[0458] The coated structures of Examples 18 and 19 have a uniform metal-carbon composite coating on the carbon substrate by immersing the carbon substrate in a material containing a metal compound and heating the immersed carbon substrate.
[0459] The attenuation rates in heat resistance test 1 for the coated structures according to Examples 1 to 6 were 10% or less, which means that no weight loss due to oxidation of the carbon substrate was observed, and the heat resistance of the carbon substrate was improved by the metal-carbon composite coating formed on the carbon substrate. On the other hand, the attenuation rates in heat resistance test 1 for the coated structure according to Comparative Example 1 and the carbon substrate according to Reference Example 1 were 17.1% and 15.8%, respectively.
[0460] The attenuation rates in heat resistance test 1 for the coated structures according to Examples 7 to 9 were slightly reduced compared to the attenuation rate in heat resistance test 1 for the carbon substrate according to Comparative Example 3. Moreover, the attenuation rate in heat resistance test 1 for the coated structure according to Example 10 was reduced to less than half of the attenuation rate in heat resistance test 1 for the carbon substrate according to Comparative Example 4.
[0461] The attenuation rates in heat resistance test 1 for the coated structures according to Examples 11 to 13 were smaller than the attenuation rate in heat resistance test 1 for the carbon substrate according to Comparative Example 5. Moreover, the attenuation rates in heat resistance test 1 for the coated structures according to Examples 14 to 17 were significantly smaller than the attenuation rate in heat resistance test 1 for the carbon substrate according to Comparative Example 6.
[0462] Furthermore, since the attenuation rates of the coated structures according to Examples 5 and 6 in heat resistance test 2 were 2% or less, no weight loss due to oxidation of the carbon substrate was observed, and the heat resistance of the carbon substrate was improved by the metal-carbon composite coating formed on the carbon substrate. On the other hand, the attenuation rates of the coated structure according to Comparative Example 1 and the carbon substrate according to Reference Example 1 in heat resistance test 2 were 2.7% and 2.7%, respectively.
[0463] The attenuation rates of the coated structures according to Examples 18 and 19 in the heat resistance test 3 and the attenuation rate of the carbon substrate according to Comparative Example 7 in the heat resistance test 3 were slightly reduced.
[0464] The results of the above-mentioned heat resistance tests 1 to 3 show that the heat resistance of the carbon substrate was improved by the metal-carbon composite coating formed on the carbon substrate, regardless of the type of metal element contained in the metal-carbon composite coating or the size and type of the carbon substrate.
[0465] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]
[0466] The metal compound-containing material according to the present invention provides a metal compound-containing material capable of forming a protective film on the carbon substrate without the need for a CVD apparatus. The metal compound-containing material according to the present invention is highly dispersible and has excellent storage stability, and suppresses the rate of defective products caused by precipitation due to changes over time, thereby reducing waste and making it possible to reduce energy costs for waste disposal. In addition, the low environmental impact and the ability to reduce waste lead to the sustainable management and efficient benefits of natural resources, as well as the achievement of decarbonization (carbon neutrality).
Claims
1. 1. A metal compound-containing composition for forming a metal-carbon composite coating on a carbon substrate, comprising: The metal compound-containing material is characterized in that the metal compound-containing material contains a compound of at least one metal element selected from the group consisting of Ti, Nb, Mo, Hf, Ta, W, Zr, and Si.
2. The metal compound-containing material according to claim 1, characterized in that the content of a compound of at least one metal element selected from Ti, Nb, Mo, Hf, Ta, W, Zr, and Si in the metal compound-containing material is more than 0 mass% and 35 mass% or less, calculated as metal.
3. 2. The metal compound-containing material according to claim 1, characterized in that the metal compound-containing material has a maximum light transmittance of 70% T or more in a wavelength range of 500 nm to 700 nm.
4. 2. The metal compound-containing material according to claim 1, wherein the particle diameter (D50) of the particles in the metal compound-containing material measured by dynamic light scattering is 3000 nm or less.
5. 5. The metal compound-containing material according to claim 1, wherein the metal compound-containing material has a pH of 6.5 or more and 13.5 or less.
6. The metal compound-containing material according to any one of claims 1 to 4, characterized in that the compound of the metal element is at least one selected from the group consisting of a peroxo complex metal compound, a metal hydroxide, a hydroxy acid complex metal compound, and a polyacid.
7. 5. The metal compound-containing material according to claim 1, further comprising an organic nitrogen compound.
8. 5. The metal compound-containing material according to claim 1, further comprising hydrogen peroxide.
9. 5. The metal compound-containing material according to claim 1, further comprising a resin.
Citation Information
Patent Citations
Manufacture of carbon products coated with silicon carbide
JP1977006714A
Method for forming thin film of titanium-containing compound
JP2005225701A
Heat resistant graphite member and manufacturing method therefor
JP2017075075A
Fuel cell, separator thereof, fuel cell sol, and manufacturing method thereof
JP2022098929A
Coating formed on graphite substrate and method for producing same
WO2017082147A1
Cited By
Support mark inspection equipment for semiconductor wafer, method for determining support mark, and program for determining support mark
CN122458755A